Multiscale experimental–numerical study of alkali-free SP flooding with sensitivity analysis in a venezuelan extra-heavy oil reservoir - A. Askarova; H. Imran; F. Rodriguez; H. Belhaj; D. Dorhjie; A. Bello; C. Yuan; C. Bejarano; R. Morales; A. Cheremisin (Fuel, 2026)

Forest conversion is more strongly associated with soil microbial functioning than chronic trace element exposure in an industrialized coastal mediterranean ecosystem - S. Fabian Plaza; F. Gonzalo Tortella; Giovanni Larama; Rodrigo Rodriguez; Thierry Lebeau; Clémentine Lapie; Walter Valdivia; Eros Fajardo; M. Fernández-Baldo; Juan Hirzel; Gustavo Santoyo; Mauricio Schoebitz (Environmental Pollution, 2026)

Lake sediment records of deglaciation and post-glacial paleoenvironmental conditions, northeast Pennsylvania, USA - Matthew S. Finkenbinder; Timothy P. Lane; Kathryn R. Adamson; Bruce P. Finney; Mark B. Abbott; Alistair J. Monteath; Adam Ianno; Cassandra N. Papp; Angus F. Fortune; Michael J. Delpais; Megan E. Novak; Angelica Y. Delgado Rodriguez; et al. (Quaternary Science Reviews, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Process monitoring of zeolite crystallization: Bridging in situ Raman spectroscopy, ex situ XRD, and predictive machine learning models - Nicolas Coca-Lopez; Fileto Rodriguez; Lars F. Lundegaard; Xiang Li; Enrique Lozano Diz; Søren Birk Rasmussen; Frederik Tielens; Monica Calatayud; Miguel A. Bañares; Raquel Portela; Pablo Beato (Chemical Engineering Journal, 2026)

Coevolving landforms, soils and vegetation: Insights into spatial patterns, feedback loops and ecosystem stability thresholds - Mariano Moreno de las Heras; José F. Rodriguez; Patricia M. Saco; Omer Yetemen; Jantiene E.M. Baartman (CATENA, 2026)

Use of recombinant gonadotropins in goat MOET programs - Shara D.E. Silva; Lucas M. Figueira; Mariana G.K. Rodriguez; Maria Eduarda A. Teixeira; Bruna W. Freitas; Ribrio Ivan T.P. Batista; Felipe Z. Brandão; Joanna M.G. Souza-Fabjan; Luiz Gustavo B. Siqueira; Jeferson F. Fonseca (Animal Reproduction Science, 2026)

Hybrid Sparrow Search Algorithm Support Vector Machine Regression Bidirectional Long-Short Term Memory (SSA-SVR-BiLSTM) model with Lagrange-based weighting for PM$$_{2.5}$$ prediction and stratified evaluation - Maria Fernanda Camargo; Sergio Diaz; Ricardo Elias Celis Parra; Vladimir Ramírez Tarazona; Astrith Eugenia Rincón Sánchez; V. Rodriguez-Rueda; Omar F. Rojas-Moreno; Alejandra Baena (Environmental and Ecological Statistics, 2026)
Air pollution is a major environmental risk to public health, strongly associated with cardiovascular and respiratory diseases. According to the World Health Organization, at least 99% of the global population lives in areas that do not meet its air-quality guidelines. PM $$_{2.5}$$ 2.5 variability reflects the interaction between local emission sources and meteorological processes that regulate near-surface dispersion and accumulation, producing nonlinear temporal patterns that motivate hybrid modeling approaches. We propose an SSA-SVR-BiLSTM framework for short-term PM $$_{2.5}$$ 2.5 forecasting that combines SSA-optimized SVR and BiLSTM models within a constrained linear ensemble with weights estimated exclusively on the validation partition using Lagrange multipliers. The model is evaluated on 10 months of high-frequency (5-min) air-quality and meteorological data collected at a traffic-influenced monitoring site in Duitama, Colombia. On the held-out test set, the hybrid achieved $$R^2 = 0.9585$$ R 2 = 0.9585 and MAPE $$= 7.62%$$ = 7.62 % , outperforming five of six SSA-optimized baselines; the difference relative to the best individual model (SSA-SVR was statistically significant but practically negligible ( $$p = 0.0105$$ p = 0.0105 , $$Δ R^2 = 0.0002$$ Δ R 2 = 0.0002 ), and the value of the hybrid lies primarily in its improved consistency across low and medium concentration regimes rather than in a large global accuracy gain. Stratified evaluation across concentration regimes and normative thresholds (WHO, EPA) revealed systematic underestimation at extreme pollution episodes, a structural limitation shared by all evaluated models. A feature occlusion analysis identified PM $$_5$$ 5 and PM $$_{10}$$ 10 as the dominant exogenous predictors (53.6 and 21.7%), with meteorological variables contributing an additional $${\sim }20%$$ ∼ 20 % of the total relevance.

Semi-supervised object-based classification of coastal dune vegetation land covers: A new hybrid labelling approach - Diego Lopez-Nieta; Emilia Guisado-Pintado; Victor F. Rodriguez-Galiano (Estuarine, Coastal and Shelf Science, 2026)

Modeling the circulation in the Magdalena–Almejas Bay System forced by tides - Susana A. Rodriguez-Melgarejo; Alejandro F. Parés-Sierra; Ana Laura Flores-Morales (Continental Shelf Research, 2026)

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

Confirmed Outbreaks of Streptococcosis Caused by Streptococcus agalactiae Serotype Ia in Nile Tilapia Culture From Campeche, Mexico - R. A. Avila‐Castillo; R. E. del Rio‐Rodriguez; S. A. Soto‐Rodriguez; J. Navarro‐Flores; A. D. Cu‐Escamilla; F. I. Marrujo‐Lopez; K. G. Aguilar‐Rendon; M. I. Gomez‐Solano (Journal of Fish Diseases, 2026)
Streptococcus agalactiae was confirmed as the etiologic agent of streptococcosis in Nile tilapia ( Oreochromis niloticus ) from Campeche, Mexico, during a cross‐sectional investigation of eight semi‐intensive farms (2021–2022) that yielded virulent strains in a challenge assay. Standard bacteriology, histopathology, API‐20 Strep phenotyping, one‐step PCR, and real‐time PCR confirmed S. agalactiae in five farms (62.5%). Gross and histological lesions were characterised by mid‐axial and peduncular muscle abscesses, extensive myonecrosis, granuloma formation, polyserositis, and occasional suppurative meningitis. Experimental infections fulfilled Koch's postulates. Juveniles of O. niloticus (20 g) infected with strain ASG‐2290 at 10 6 CFU/mL produced 53% mortality at 96 h. Whole‐genome sequencing of the strains ASG‐2290 and ASG‐2292 identified them as S. agalactiae Ia, marking the first report of this serotype isolated from farmed tilapia in Mexico. Frequent interstate fry movements are likely to be a risk factor for pathogen dissemination. These findings document the geographic expansion of pathogenic S. agalactiae into the Yucatan Peninsula, underscoring the need for strengthened surveillance, biosecurity, and diagnostic capacity to mitigate economic losses in Mexican tilapia aquaculture. Considering that tilapia aquaculture is carried out all year‐round in the Yucatan Peninsula, the implications of these findings are of major concern.

A GIS–AHP Framework for Sustainable Well Placement: Application for Natural Gas and Hydrogen Exploration in the Eastern Cordillera Basin, Colombia - Salim A. Salon; Sebastian S. Rodriguez; Jhon M. Muñoz-Barrera; Fabián Gallego; Cesar Mora; Deysi P. Forero; Jose F. Osorno; Cristian Peñafort (Natural Resources Research, 2026)

Development of an ELISA as a complement to MAT for swine leptospirosis diagnosis - Micaela Esteban; Cristina Sanchez; Marcelo A. Rodriguez; Vanina R. Saraullo; Micaela Hamer; Bibiana F. Brihuega; Luis Samartino; Mara L. Martinez (Research in Veterinary Science, 2026)

Advancing Coronary Risk Assessment Through Combined Radiomic, Mechanical, and Hemodynamic Analysis - Anna Corti; Marco Stefanati; Vittorio Lissoni; Matteo Leccardi; Francesco Bruno; Alessandro Depaoli; Pietro Cerveri; Francesco Migliavacca; Valentina D. A. Corino; José F. Rodriguez Matas; Luca Mainardi; Gabriele Dubini (Annals of Biomedical Engineering, 2026)
Purpose Detecting vulnerable coronary plaques through coronary computed tomography angiography (CCTA) is a crucial, yet challenging task. To date, most of the proposed vulnerability markers have been studied in isolation. This study introduces the first integrated analysis combining radiomic, mechanical, and hemodynamic factors to explore their synergistic contribution to plaque vulnerability. Methods The study analyzed 161 plaques in 46 coronary arteries from 39 patients, with 7 arteries (28 plaques) from 7 individuals, labeled as vulnerable from intravascular imaging. First, CCTA radiomic features were extracted. Second, mechanical markers were computed through finite element simulations conducted with varying material characteristics, accounting for the arterial wall mechanical properties’ uncertainties. Third, hemodynamic markers were derived from transient computational fluid dynamics simulations. Finally, a machine learning pipeline was developed to classify coronary arteries and patients based on radiomic, mechanical, and hemodynamic features, both individually and in combination. Results Radiomics achieved the highest sensitivity (1.00), with all vulnerable patients identified, but lower specificity (0.69). Differently, mechanics and hemodynamics achieved higher specificities (0.94 and 0.97, respectively) but lower sensitivities (both 0.86). By integrating at least two out of the three models, the predictive performance improved, up to sensitivity = 1.00 and specificity = 0.97, with only one misclassified case. Conclusion Although based on only 39 patients, the results highlight the power of a multi-level integrative approach for coronary plaque assessment. The study revealed that (i) hemodynamics outperformed mechanics and radiomics; (ii) while radiomics maximized sensitivity, mechanics and hemodynamics prioritized specificity, and (iii) integrating at least two variable types added value.

Per- and polyfluoroalkyl substances and pesticides in black bears (Ursus americanus) and grizzly bears (Ursus arctos horribilis) from Montana's Cabinet-Yaak ecosystem: A baseline assessment of emerging and legacy contaminants - Brian C. Balmer; Marina D. Rodriguez; Justin E. Teisberg; Michelle L. Hladik; Wayne F. Kasworm; Amber Kornak; Thomas G. Radandt; Landon M. Keele; Erin L. Pulster (Environmental Pollution, 2026)

Transcriptomic response of Acropora cervicornis following transplantation to a marginal, nearshore environment - Allyson DeMerlis; Colin Foord; Dalton J. Hesley; Richard F. Karp; Lys M. Isma; Natalia Andrade-Rodriguez; Kevin H. Wong; Michael S. Studivan; Mike Jankulak; Andrew C. Baker; Diego Lirman; Nikki Traylor-Knowles; et al. (Frontiers in Marine Science, 2026)
As reef-building coral cover has declined worldwide, coral restoration has become a widespread response towards repopulating degraded reefs. In-situ nurseries have provided refugia for the regrowth of several coral species, yet long-term success following outplanting remains highly variable, particularly when corals are introduced into novel or marginal environments. Additionally, while growth and survivorship are commonly used to evaluate restoration success, molecular responses may also provide critical insights into the capacity of corals to acclimatize following transplantation. Here, we examined host and algal symbiont gene expression in the critically endangered reef-building coral Acropora cervicornis following transplantation from an offshore nursery in Key Biscayne, Florida to a nearshore, urbanized habitat in the Port of Miami, Florida. Three nursery-propagated genotypes were outplanted in June 2021 and sampled after four months at both sites for transcriptomic analysis ( n =12 after quality filtering). Transplanted corals exhibited significant shifts in host gene expression relative to nursery controls, with 961 host and symbiont genes significantly upregulated and 165 significantly downregulated. Upregulated host genes were predominantly associated with the environmental stress response, including heat shock proteins, unfolded protein binding, apoptotic processes, detoxification pathways, and innate immune signaling. Weighted gene co-expression network analysis identified two host modules positively associated with the nearshore outplant site and were enriched for pathways related to protein folding, immune activity, and cellular reorganization. These results demonstrate that A. cervicornis outplanted to a nearshore, urbanized environment exhibits sustained activation of stress- and immune-related molecular pathways months after transplantation, which is consistent with a stress-response profile that may reflect ongoing acclimatization. Integrating molecular diagnostics with environmental monitoring may refine genotype and site selection to enhance restoration outcomes.

Pheromone trail following is not modulated by previous visit to food location, distance travelled, or travel direction in the ant Lasius niger - L.-A. Poissonnier; D. Winter; F.‑J. Olivera‑Rodriguez; C. Werneke; T. J. Czaczkes (Insectes Sociaux, 2026)
Ant foraging and recruitment often relies heavily on pheromone trails, and ants modulate pheromone trail deposition strategically. Ants are also known to modulate trail following depending on their own private information, such as the known location of the nest and their knowledge of food sources in the environment. Here we ask how a series of important context variables—distance from the nest, direction of travel, and prior food discovery—affects the fidelity of pheromone trail following in the black garden ant Lasius niger . Using both an open arena assay and a binary Y-maze design, we evaluated whether ants adjust their trail-following behaviour. Ants exhibited robust and consistent trail-following behaviour across all conditions. Surprisingly, we found no significant modulation by distance, travel direction, or recent experience. However, we observed that distance travelled before finding a pheromone trail significantly influenced subsequent walking patterns such as straightness, speed, and total distance travelled. These findings suggest that while L. niger trail-following behaviour is remarkably stable across contexts, locomotory traits remain plastic and context-sensitive. The decoupling of pheromone response from internal or external conditions highlights the need for further investigation into the mechanisms regulating individual foraging decisions in social insects.

Comparative evaluation of sperm quality assessment methods in purebred spanish horses - N. Latorre; C. Gómez-Cuétara; E. Cañizares; F. Crespo; V. Pérez-Aguilera; M. Iniesta Cuerda; J.A. Laborda-Gomariz; A.J. Soler; E.R.S. Roldan; A. Sanchez-Rodriguez (Journal of Equine Veterinary Science, 2026)

Morphology and particle size distribution in the indoor dust: A hidden threat to human health? - D. Meza-Figueroa; E. Vega; J. Entwistle; A. Angulo-Molina; A. Valencia-Meza; B. Schiavo; V. Rodriguez; B. González-Grijalva; F. Berrellez-Reyes; C. Ortega-Rosas; A. Wellens; A. Namdeo (Environmental Geochemistry and Health, 2026)

Deacetylation and Mechanical Refining Pathway for the Bioconversion of Sugarcane Bagasse - Fernando Roberto Paz Cedeno; Gustavo R. Gomes; Jessica J. Silva; Fabricia F. Menezes; Viviane M. Nascimento; George J. M. Rocha; Renata P. Rodriguez; Xiaowen Chen; Antonio Bonomi; Carlos Driemeier (BioEnergy Research, 2026)
Advancing lignocellulose biorefining is imperative for the deployment of cellulosic (2G) biofuels. This work investigates the tailoring of the alkaline deacetylation and mechanical refining (DMR) pathway for the bioconversion of sugarcane bagasse. Experiments are conducted at laboratory and pilot scales, varying the pretreatment conditions (70–92 °C; 48–100 g NaOH /kg) and the mechanical refining technologies (PFI and disk refining). The pretreatments selectively solubilize acetyl groups (> 86%) and lignin (10–63%) while mostly preserving structural carbohydrates in the solid phase. Enzymatic hydrolysis generates hydrolysates of clean sugars (glucose and xylose), with sugar yields increasing up to 81% for glucose and 89% for xylose in response to delignification and mechanical refining. Biochemical methane potential assays reveal specific methane productions of up to 568 NmL CH₄ gVS⁻¹ for alkaline liquor monodigestion and 344 NmL CH₄ gVS⁻¹ for co-digestion with sugarcane vinasse from the conventional (1G) sugarcane ethanol, indicating a strong potential for bioenergy recovery from this process stream. Synergies are identified in integrating 1G ethanol, 2G DMR processing of bagasse, and anaerobic co-digestion of 1G vinasse and 2G DMR alkaline liquor. This technology enables sugarcane biorefineries to enhance the co-production of ethanol, methane, and concentrated streams of CO 2 .

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Activation of Toll-like receptor 2 reveals microbial contamination beyond endotoxins on micro- and nanoplastics - Øyvind P. Haugen; Itziar Polanco-Garriz; Victor Alcolea-Rodriguez; Raquel Portela; Rita Bæra; Hamed Sadeghiankaffash; Jana Hildebrandt; Dmitri Ciornii; Korinna Altmann; Francesco Barbero; Ivana Fenoglio; Julián J. Reinosa; et al. (Toxicology in Vitro, 2026)

Enzyme-assisted extraction of inulin from dahlia (Dahlia sp.) tuber with prebiotic activity - Carlos Neftali Cano-Gonzalez; Raul Rodriguez-Herrera; Armando Quintero-Ramos; Adriana Carolina Flores-Gallegos; Francisco Castillo-Reyes; Sebastian F. Cavalitto; Dinesh Yadav; Juan Carlos Contreras-Esquivel (Biocatalysis and Agricultural Biotechnology, 2026)

Spatial Modeling of Sugarcane Yield Using Machine Learning Approaches - Diego A. Socadagui-Casas; Andres F. Rodriguez-Vasquez; Yolanda Rubiano-Sanabria; Daniel M. Jimenez-Gutierrez; Sonia R. Socadagui-Casas (Sugar Tech, 2026)
Sustainable precision agriculture and artificial intelligence (AI) are transforming modern farming by enhancing resource efficiency, addressing climate challenges, and fostering sustainability. In Colombia, sugarcane cultivation is pivotal in the agricultural economy, particularly in the Cauca River Valley, a region grappling with climate variability and resource optimization challenges. This study introduces an innovative methodology that combines machine learning (ML) techniques with geospatial data to predict sugarcane yields accurately. The research employs the CatBoost, random forest, and XGBoost ML algorithms, integrating historical data on climate, soil characteristics, and agricultural management practices to develop spatially detailed predictive models. The findings demonstrate that ML-based approaches outperform traditional methods like linear and penalized regressions, offering more precise agricultural planning and resource management predictions. Focused on the municipality of La Candelaria, this work underscores the potential of ML technologies to enhance productivity while promoting sustainable agriculture.

Designing robust energy policy packages under deep uncertainty: A multi-metric decision support framework - Antonio F. Rodriguez-Matas; Thomas B. Wild; Pedro Linares; Jonathan R. Lamontagne; Claudia Dominguez-Barbero (Energy Policy, 2026)

Governance Arrangements That Fit Social‐Ecological Context Are Associated With Fishery Sustainability - Mateja Nenadović; Alfredo Giron; Timothy Frawley; Adrian Munguia‐Vega; Kara E. Pellowe; Erica Ferrer; David Gill; Blanca González‐Mon; Andrew F. Johnson; Emilie Lindkvist; Fiorenza Micheli; Amy H. Weaver; et al. (Fish and Fisheries, 2026)
In many parts of the world, natural resources are primarily managed by governance arrangements at the local level. Those arrangements range from collective, such as cooperatives and associations, to individualistic, such as patrons and owner‐operators. A key question is how such arrangements influence resource use and associated social and ecological outcomes. We hypothesize that sustainable resource use is not associated with a specific governance arrangement, but instead that every type of arrangement has a certain set of social and ecological conditions under which sustainable resource use is feasible. This hypothesis was empirically investigated using fisheries landings data from Mexico. We found that sustainable resource use can be achieved through multiple governance arrangements provided that they are matched to appropriate social‐ecological contexts. Our findings help identify which governance arrangements are best suited to particular contexts and provide the initial building blocks for developing a theory of governance contextual fit in social‐ecological fishing systems.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Hydrologic connectivity as a predictor of degradation thresholds across semiarid sites with different vegetation patterns - Samira Azadi; Patricia M. Saco; Mariano Moreno-de las Heras; Jose F. Rodriguez (CATENA, 2026)

Correction to: The Neuronal Ischemic Tolerance Is Conditioned by the Tp53 Arg72Pro Polymorphism - Maria E. Ramos-Araque; Cristina Rodriguez; Rebeca Vecino; Elisa Cortijo Garcia; Mercedes de Lera Alfonso; Mercedes Sanchez Barba; Laura Colàs-Campàs; Francisco Purroy; Juan F. Arenillas; Angeles Almeida; Maria Delgado-Esteban (Translational Stroke Research, 2026)

Forecasting the Biological Effect of PEGylated-rHuEPO Candidates in Chronic Kidney Disease Patients using a Middle-out Translation Approach - Gledys Reynaldo-Fernandez; Leyanis Rodriguez-Vera; Daniel Amaro; Joaquin Solozábal; Jorge Duconge; Victor Mangas-Sanjuan; Iñaki F. Troconiz; Francine Johansson Azeredo; Valvanera Vozmediano (Pharmaceutical Research, 2026)

Quantifying Time-Lagged Vegetation Responses to Hydroclimatic Factors in Dam-Influenced Arid Regions Using VAR Modeling and Remote Sensing - Raid Almalki; Mehdi Khaki; Patricia M. Saco; Jose F. Rodriguez (Environmental Management, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

High frequency of plastic-derived contaminants (phthalate acid esters) in the preen gland of dead procellariiform seabirds from the Patagonian Sea - Luciana Gallo; María Rosa Repetti; Melina Paola Michlig; Leandro L. Tamini; Leandro N. Chavez; Ruben F. Dellacasa; C. Karina Alvarez; Sergio A. Rodriguez Heredia; Ralph Eric Thijl Vanstreels; Patricia Pereira Serafini; Marcela M. Uhart (Marine Pollution Bulletin, 2026)

Assessment of mercury (Hg) contamination in tropical areas of the Eastern Pacific and Southwestern Atlantic oceans using two species of sea turtles - César Augusto Barrios-Rodriguez; Moisés F. Bezerra; Eric Enrique Flores; Carlos Antonio Vigil-González; Wilfredo Poveda-Pineda; Joelbin de la Cruz; Carlos Eduardo de Rezende; Marcelo Gomes de Almeida; Wanderley Rodrigues Bastos; Luiz Drude de Lacerda (Marine Pollution Bulletin, 2026)

Identifying and quantifying greenhouse gas emissions with the AVIRIS-3 airborne imaging spectrometer - Red Willow Coleman; Andrew K. Thorpe; Philip G. Brodrick; Adam Chlus; Jay E. Fahlen; Brian Bue; John Chapman; Regina F. Eckert; Daniel J. Jensen; Michael L. Eastwood; David R. Thompson; Clayton D. Elder; et al. (Remote Sensing of Environment, 2026)

Biochar enhances nitrogen use efficiency in lettuce by promoting its metabolic assimilation - Alvaro F. Garcia-Rodriguez; Francisco J. Moreno-Racero; Rosario Álvarez; José M. Colmenero-Flores; Heike Knicker; Miguel A. Rosales (Plant and Soil, 2026)
Background and aims Peat replacement with biochar (BC) offers a sustainable strategy in horticultural substrates but its effects on plant nitrogen (N) metabolism and N use efficiency (NUE) remain unclear. This study tested whether vineyard-pruning-derived BC can boost NUE and metabolic activity in lettuce, providing a pathway toward more productive and sustainable horticulture. Methods Plant substrates (BC, peat and vermiculite) were prepared in the following proportions (v:v:v): B0 (0:70:30), B15 (15:55:30) and B30 (30:40:30) for growing lettuce (Lactuca sativa L. var. Batavia) under greenhouse conditions for 31 days. We assessed plant growth and physiological traits, quantified N species and calculated NUE parameters and the activities of key N assimilation enzymes. Results B30 plants produced 44.2% more biomass and 23.2% larger leaf area than B0, resulting in lower specific leaf area and greater succulence. BC addition decreased available NO₃⁻ and NH₄⁺ in substrate and roots without causing any plant stress symptoms, as chlorophyll content and PSII efficiency remained stable. B30 increased N uptake flux, N utilization efficiency, partial N balance, and N productivity by 31.8%, 34.8%, 27.8%, and 13.8%, respectively, relative to B0, coinciding with enhanced N-assimilation enzymatic activity. Despite lower total N in roots and shoots, protein accumulation increased, indicating more efficient N conversion into organic compounds. Conclusion These findings demonstrate the potential of BC-based substrates (especially 30% BC) to enhance lettuce productivity by improving NUE through the stimulation of N assimilation pathway, offering a promising strategy to optimize N-fertilizer needs to support more sustainable agriculture and soil management practices.

Addition discarded tennis balls as an inert bulking agent to olive mill waste and pig slurry during composting reduces the energy consumption related to ventilation and the generation of anaerobic gases - Juan Aviñó-Calero; Ernesto Santateresa; Luciano Orden; Evan A.N. Marks; Encarnación Martínez-Sabater; F. Javier Andreu-Rodriguez; José Antonio Saéz-Tovar; María Dolores Pérez-Murcia; María Ángeles Bustamante; Raúl Moral (Journal of Environmental Management, 2025)

The CALHM1 blocker CGP37157 increases seizure severity during status epilepticus in adult mice - Meghma Mitra; Amaya Sanz Rodriguez; Norman Delanty; Alan Beausang; Francesca M. Brett; Michael A. Farrell; Jane Cryan; Donncha F. O’Brien; David Henshall; Maria F. Cano-Abad; Tobias Engel (Purinergic Signalling, 2025)
Epilepsy is one of the most common chronic brain diseases affecting up to 70 million people worldwide. Major challenges of epilepsy treatment include the high pharmacoresistance in patients and the lack of disease-modification. Extracellular adenosine 3’triphosphate (ATP), a key neurotransmitter in the activation of the purinergic signalling system, is increasingly recognized to contribute to pathological brain hyperexcitability in epilepsy. Consequently, targeting ATP-release mechanisms may constitute a new therapeutic strategy for seizure control and epilepsy. The calcium channel, Calcium Homeostasis Modulator 1 (CALHM1), a voltage-gated, non-selective ion channel that permits the passage of various cations and small molecules, is expressed in neurons and plays an essential role during neuronal excitability and neurotransmission. In addition to ions, CALHM1 also allows the passage of ATP into the extracellular space, activating thereby purinergic receptors. Here, we tested if the pharmacological blocking of CALHM1 via CGP37157 (7-chloro-5-(2-chlorophenyl)-3,5-dihydro-4,1-benzothiazepin-2-(1H)-one) alters the severity of intra-amygdala kainic acid-induced status epilepticus. Our results show that CGP37157 increased the severity of seizures during status epilepticus. In addition, CALHM1 protein levels are down-regulated in the hippocampus in epileptic mice and Temporal Lobe Epilepsy (TLE) patients. In summary, our results identify CALHM1 as a new contributor to seizures and suggest targeting of CALHM1 as new treatment strategy for epilepsy.

A Simple Model to Estimate the Economic Optimum Nitrogen Rate in Potato Using Vegetation Indices - Claudia M. Giletto; W. D. Carciochi; F. M. Inchauspe; S. E. Silva; M. N. Cassino; V. Ortega; S. Rodriguez; J. C. Laborde Amador; N. Reussi Calvo (Potato Research, 2025)

Cause-effect relationship between volcanism and travertine-tufa deposition: the case study of Barranco de Azuaje, Gran Canaria, revisited - F. J. Perez-Torrado; M. C. Cabrera; A. Rodriguez-Gonzalez; Á. Marrero-Rodríguez; C. Ravazzi; P. Vidal-Matutano; J. L. Fernandez-Turiel (Journal of Iberian Geology, 2025)

Correction to: Hydrogeochemical Evaluation of an Urban Aquifer Under Stress: Rare Earth Elements Fractionation and Human Health Implications - K. M. Ochoa-Guerrero; P. F. Rodriguez-Espinosa; E. Martinez-Tavera; V. Balaram; M. P. Jonathan (Environmental Management, 2025)

Hydrogeochemical Evaluation of an Urban Aquifer Under Stress: Rare Earth Elements Fractionation and Human Health Implications - K. M. Ochoa-Guerrero; P. F. Rodriguez-Espinosa; E. Martinez-Tavera; V. Balaram; M. P. Jonathan (Environmental Management, 2025)

Soft Range Limits Shape Sensitivity to Forest Cover More Strongly Than Hard Range Limits - Natasha R. Granville; Alex L. Pigot; Benjamin Howes; Luiz dos Anjos; Victor Arroyo‐Rodriguez; Luc Barbaro; Jos Barlow; Matthew G. Betts; Alexis Cerezo; Pedro F. Develey; Jack H. Hatfield; Hervé Jactel; et al. (Global Ecology and Biogeography, 2025)
Aim Land‐use change is a major threat to biodiversity, yet there remains considerable unexplained variation in how it affects different populations of the same species. Here, we examine how sensitivity to forest cover changes depending on proximity to different limits of a species' range. By comparing responses as species approach their coastal (‘hard’) and inland (‘soft’) range limits, we aim to provide insight into the relative influence of mass effects, as compared to abiotic and biotic environmental suitability in shaping population sensitivity. Location Global. Time Period 1996–2019. Major Taxa Studied Birds. Methods We combined data from several large databases to obtain a dataset of 2543 bird species surveyed across 116 studies, spanning six continents. Using expert‐verified range maps, we calculated the position of populations relative to their species' nearest inland (‘soft’) and coastal (‘hard’) range limits and categorised the inland limits as equatorward‐ or poleward‐ facing. We investigated how distance to range limits and forest cover, derived from a 30 m‐resolution global dataset, affect the probability of species' incidence. Results We found that bird populations are more sensitive to forest cover when located closer to their species' inland (‘soft’) range limits, whereas this was not the case at coastal (‘hard’) range limits. The heightened sensitivity to forest cover at soft range limits was similar regardless of whether the range limit faced equatorward or poleward. Main Conclusions These results highlight how populations close to the soft limits of their species' ranges are at higher risk of extirpation resulting from loss of forest cover. This suggests that environmental conditions (e.g., climate), which become more challenging away from the core of the species' range, drive variability in sensitivity to forest cover.

Integrated Population Pharmacokinetic-pharmacodynamic Modeling of HIV Virus-host Infection Dynamics in Patients Undergoing Antiretroviral Monotherapy - Alberto Vegas Rodriguez; Nieves Velez de Mendizábal; Yanan Zheng; Jason T. Hindman; Ramesh Palaparthy; John Ling; Iñaki F. Trocóniz; Ana Ruíz-Garcia; Justin S. Feigelman (The AAPS Journal, 2025)
Chronic human immunodeficiency virus (HIV) infection continues to pose a major global health challenge, with an estimated 39.9 M cases and 1.3 M new infections per year. Up to 75%, of people with HIV (PWH) are currently being treated with antiretroviral therapy. The development of effective treatments for HIV requires a detailed understanding of the virus-host interaction. Often, mathematical models are used to inform this understanding as well as to characterize therapeutic response. This work aims to develop a single and fully identifiable population semi-mechanistic pharmacokinetic/pharmacodynamic (popPKPD) model integrating data (drug levels, CD4 + T cells and viral RNA) of five different antiretroviral (ARV) drugs administered in monotherapy: lenacapavir, bictegravir, tenofovir alafenamide, emtricitabine and elvitegravir. Data were obtained from six phase 1 clinical studies and model development was performed using NONMEM 7.5.1. The viral dynamics were best described by expanding the “basic” viral dynamics model with two more populations of infected cells: chronically and latently infected. Obtained death rates values of infected cells & virus were consistent with literature values. Population baseline HIV-RNA was estimated to be 43,460 copies/mL, with an IIV of 141%, the estimated baseline concentrations of CD4 + cells varied largely across the different cell types in the model: 410, 20, 7 and 7 cells/mL for uninfected, infected, chronic and latently infected cells, respectively. The popPKPD model was able to capture key aspects of viral dynamics, drug behaviour, and treatment response. The models developed will serve as a useful tool for further development and optimization of these HIV therapies, especially when evaluating multiple ARVs to be administered in a novel combination setting. Graphical Abstract

Biogenic nanoparticles: Synthesis, characterization, applications and scaling up limitations in water treatment - Alejandra Ortiz-Tirado; Luisa F. Medina-Ganem; Erick R. Bandala; Alain S. Conejo-Davila; Alejandro Vega-Rios; Ashantha Goonetilleke; Oscar M. Rodriguez-Narvaez (Journal of Environmental Chemical Engineering, 2025)

Evaluating the role of physical mechanisms as possible triggers for turbidity currents in a deep ocean seamount - Susana M. Lebreiro; Álvaro Peliz; Laura Antón; Sílvia Nave; M. Isabel Reguera; Rocío Lozano-Luz; Claire Waelbroeck; Simon Crowhurst; Belen Martrat; Jordi F. Lopez; Raphaël Hebert; Alejandra Lopez-Rodriguez (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

P20-17 Polyethylene terephthalate (PET) nanoplastics induce acute pulmonary inflammation in mice - Ø.P. Haugen; L.M.A. Camassa; H.F. Berntsen; F.-C. Lin; V. Alcolea-Rodriguez; R. Portela; F. Barbero; O.A.H. Foss; H. Sadeghiankaffash; Ø. Skare; S. Alsaedi; A.L. Moen; et al. (Toxicology Letters, 2025)

Foliar-Application of Proline Mitigates Salinity Stress in Two Maize (Zea mays L.) Genotypes: A Comparative Study of Growth, Physiology, Chlorophyll Fluorescence, and Ionic Composition - Tayyaba Naz; Muhammad Mazhar Iqbal; Iftikhar Ahmad; Muhammad Adnan Sohail; Shazia Iqbal; Aftab Jamal; Luis Alfonso Rodriguez-Paez; Marcelo F. Pompelli (Journal of Plant Growth Regulation, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Removal of PFAS and pharmaceuticals from municipal wastewater using a novel β-cyclodextrin adsorbent over distinct contact times - Emma F. Shapiro; Zhi-Wei Lin; Edwin Saavedra Cifuentes; Francisco J. Barajas-Rodriguez; Rosa Gwinn; William R. Dichtel; Aaron I. Packman (Water Research, 2025)

Active and passive pathways of nutrient transfer in coral reef ecosystems - Ruth E. Dunn; Nicholas A. J. Graham; Laura-Li Jeannot; Rucha Karkarey; F. Javier Gonzalez-Barrios; Ines D. Lange; Julia Rodriguez Fillol; Ronan Roche; Marleen Stuhr; Cassandra E. Benkwitt (Coral Reefs, 2025)
Coral reefs receive both passive and active nutrient subsidies, supplied via oceanographic processes and animal-mediated transfer, which can bolster reef productivity and resilience to disturbance. We examined the relative importance of these two pathways across lagoonal and seaward reefs, reefs of different depths, and those around islands either with or without breeding seabird colonies using carbon and nitrogen stable isotopes (ð 13 C and ð 15 N) and nutrient metrics (per cent N, %N and carbon-to-nitrogen ratios, C:N). We found increased passive oceanic nutrient inputs in reefs that were both deep and seaward facing, indicated by lower ð 13 C values. Enriched ð 15 N values and lower carbon-to-nitrogen ratios within reefs adjacent to islands with seabird colonies provided evidence of the role of seabirds as active vectors of nutrients to coral reef food webs, particularly within shallow, lagoonal reefs. Though %N values did not seem to provide a good indicator through which to disentangle active vs passive nutrient transport within this context, variation in ð 13 C and ð 15 N values and C:N ratios highlighted the interplay between passive oceanic processes and active seabird contributions to coral reefs. We emphasise the importance of both preserving and restoring natural nutrient pathways, particularly at a time when coral reef ecosystems are under increasing pressure from anthropogenic threats.

Visible light photosensitised cross-flow microfiltration membrane reactors for managing microplastic-contaminated bio-effluents - Hooralain Bushnaq; Sisi Pu; Tom Burton; Julio Rodriguez-Andres; Julio Carrera Montoya; Jason Mackenzie; Catherine Munro; Giovanni Palmisano; Srinivas Mettu; James Mcelhinney; Ludovic F. Dumée (Water Research, 2025)

Dynamic effect of climate change on flood damage cost in the Andean region of Colombia using an ARDL-ECM model and climate change projections - Camilo A. Rodriguez-Espinosa; Carlos F. Valencia; Carlos G. Ramirez; Carlos D. Valencia (Sustainable Cities and Society, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Association between PFAS exposure and metabolic-related biomarkers in Spanish adolescents - Andrea Rodriguez-Carrillo; Fernando Vela-Soria; Fatima Smagulova; Mariana F. Fernández; Carmen Freire (Environmental Research, 2025)

Leveraging passive acoustic monitoring for result-based agri-environmental schemes: Opportunities, challenges and next steps - Anna F. Cord; Kevin Darras; Ryo Ogawa; Luc Barbaro; Charlotte Gerling; Maria Kernecker; Nonka Markova-Nenova; Gabriela Rodriguez-Barrera; Felix Zichner; Frank Wätzold (Biological Conservation, 2025)

Venom variation and ontogenetic changes in the Crotalus molossus complex: Insights into composition, activities, and antivenom neutralization - Miguel Borja; Gamaliel Castañeda-Gaytán; Alejandro Alagón; Jason L. Strickland; Christopher L. Parkinson; Areli Gutiérrez-Martínez; Bruno Rodriguez-López; Vanessa Zarzosa; Bruno Lomonte; Anthony J. Saviola; Julián Fernández; Cara F. Smith; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Safety Outcomes of Antiplatelet Therapy During Endovascular Treatment of Tandem Lesions in Acute Ischemic Stroke Patients - Mudassir Farooqui; Afshin A. Divani; Milagros Galecio-Castillo; Ameer E. Hassan; Mouhammad A. Jumaa; Marc Ribo; Michael Abraham; Nils Petersen; Johanna Fifi; Waldo R. Guerrero; Amer M. Malik; James E. Siegler; et al. (Translational Stroke Research, 2025)

Thermal analysis of multi-layered glazed window under Mexican climate - I. Zavala-Guillén; D. Barrera-Román; F. Noh-Pat; Miguel Sidón; D. García-Pérez; A. Rodriguez-Ake (Energy and Buildings, 2025)

Unveiling the biogas potential of raw Agave leaf juice: Exploring a novel biomass source - Maiki S. de Paula; Oscar F. Herrera Adarme; Maria Paula C. Volpi; Carla I. Flores-Rodriguez; Marcelo F. Carazzolle; Gustavo Mockaitis; Gonçalo A.G. Pereira (Biomass and Bioenergy, 2025)

Evaluation of intra- and inter-rater agreement on ultrasound measurements of dairy cow teats by operators with different experience levels - I. Nocera; G. Sala; C. Orsetti; J. M. Rodriguez-Lopez; M. Sgorbini; F. Bonelli (Veterinary Research Communications, 2025)

Understanding Environmental Factors Influencing Vegetation Cover Downstream of Dams - Raid Almalki; Mehdi Khaki; Patricia M. Saco; Jose F. Rodriguez (International Journal of Environmental Research, 2025)

Bridges monitoring and assessment using an integrated bim methodology - D. Rodriguez Polania; F. Tondolo; A. Osello; M. Piras; V. Di Pietra; N. Grasso (Innovative Infrastructure Solutions, 2025)
Risk assessment of long-existing infrastructure has become one of the main challenges in civil engineering. Major efforts have been made in recent years to develop new techniques for rapid damage identification and ensure proper management of these structures. This paper presents a data management approach utilizing BIM methodology to create a digital database for bridge monitoring procedures. Initially, two BIM methodologies for creating a damage database are introduced, focusing on beams from a dismantled urban viaduct. Subsequently, the most suitable methodology is applied to an existing bridge in Turin, Italy. Through the chosen methodology a damage identification and classification process based on a triangular mesh is performed, assisted by a convolutional neural network (CNN) for automatic damage detection. Additionally, the paper outlines a digitalization process within a BIM environment, integrating official guidelines for bridge risk evaluation, classification, and monitoring in Italy. By employing programming tools, all data required by the guidelines is efficiently incorporated into the database. The outcomes demonstrate the effectiveness of remote sensing applications for bridge inspection and the possibility of merging BIM methodology into the inspection process to enhance the damage assessment of existing structures.

Making waves: Harnessing stormwater for resilient water supply - A blueprint for vulnerable continental coasts and oceanic islands - Lisitai Yang; Enrique Rodriguez Quinones; Evan B. Yao; Qiufeng Lin; Zepei Tang; Walter F․Silva Araya; Yang Deng (Water Research, 2025)

Bacterial dynamics and volatile metabolome changes of vacuum-packaged beef with different pH during chilled storage - Magdevis Y. Rodriguez-Caturla; Larissa P. Margalho; Juliana S. Graça; Arthur K.R. Pia; Viny L. Xavier; Melline F. Noronha; Lucélia Cabral; Wilson J.F. Lemos-Junior; Carmen J.C. Castillo; Anderson S. SantˈAna (International Journal of Food Microbiology, 2025)

Focal pharmacological manipulation of serotonin signaling in the amygdala does not alter social behavior - Jessica T. Jacobs; Rafael S. Maior; Hannah F. Waguespack; Carolina Campos-Rodriguez; Ludise Malkova; Patrick A. Forcelli (Psychopharmacology, 2025)

High frequency of plastic ingestion in procellariiform seabirds (albatrosses, petrels and shearwaters) in the Southwest Atlantic Ocean - Luciana Gallo; Patricia P. Serafini; Ralph E.T. Vanstreels; Leandro L. Tamini; Cristiane K.M. Kolesnikovas; Alice Pereira; Tatiana Neves; Gabriel D. Nascimento; Lucas S. Rodriguez Pirani; A. Lorena Picone; Rosana M. Romano; C. Karina Alvarez; et al. (Marine Pollution Bulletin, 2024)

Effect of aging time on the physicochemical properties of lime used to preserve corn postharvest - Efren Herrera-López; Sylvanus Odjo; Luis F. Zubieta-Otero; Brenda L. Contreras-Jiménez; Fabiola Curiel-Ayala; Lina Garcia-Mier; Mario E. Rodriguez-Garcia (Journal of Stored Products Research, 2024)

Auxin-Mediated Modulation of Maize Rhizosphere Microbiome: Insights from Azospirillum Inoculation and Indole-3-Acetic Acid Treatment - Anahí Coniglio; Giovanni Larama; Sofía Nievas; Natalie L. Cale; Verónica Mora; Daniela Torres; Gastón Lopez; Florencia Donadio; Belén Rodriguez; Anelis Marin; Matias Rovere; Patricio Javier Barra; et al. (Journal of Soil Science and Plant Nutrition, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Extraction of bio-hydroxyapatite from devilfish (Loricariidae) for the fluoride and cadmium adsorption from water and its feasible photocatalytic properties - Hilda G. Cisneros-Ontiveros; Luis F. Zubieta-Otero; Nahum A. Medellín-Castillo; Alfredo I. Flores-Rojas; Mario E. Rodriguez-Garcia (Chemosphere, 2024)

Time-dependent analytical solutions for tunnels excavated in anisotropic rheological rock masses - G.S. Zeng; H.N. Wang; F. Song; A. Rodriguez-Dono (Tunnelling and Underground Space Technology, 2024)

Cardiac alterations induced by Heloderma horridum horridum venom in rats: An experimental study with ECG analysis using a linear regression algorithm - Karla Isabel Vazquez-Gonzalez; Alberto Ochoa-Brust; Alejandrina Rodriguez-Hernandez; Hugo Ventura-Cisneros; Gisela Jareth Lino-Lopez; Rafael Barbosa-Valdovinos; Armando Rodriguez-Vazquez; Oscar F. Vazquez-Vuelvas; Ramon A. Felix; Juana M. Jiménez-Vargas; Valery Melnikov; Laura Leticia Valdez-Velazquez (Toxicon, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Analytical solutions of noncircular tunnels in transversely isotropic rheological rock masses - G.S. Zeng; H.N. Wang; F. Song; A. Rodriguez-Dono; L.R. Alejano (International Journal of Rock Mechanics and Mining Sciences, 2024)

Distribution and development patterns in sea stars (Echinodermata: Asteroidea) of the Subantarctic Southern Atlantic - Cintia P. Fraysse; Claudia C. Boy; Mariel A. Ojeda; Mariano Rodriguez; Javier H. Rojo; Analía F. Pérez (Polar Biology, 2024)

Transcriptomic responses to hypoxia in two populations of eastern oyster with differing tolerance - Emma L. Crable; Heather Rodriguez; Rujuta V. Vaidya; Nicholas Coxe; Jerome F. La Peyre; Morgan W. Kelly (Frontiers in Marine Science, 2024)
The eastern oyster, Crassostrea virginica , is a keystone species native to the Gulf of Mexico and Atlantic coasts of the United States and Canada. It provides habitat for other marine organisms and makes up the majority of oyster production in the United States. Despite its tolerance to hypoxic conditions, C. virginica is threatened by anthropogenic climate change, which is increasing both average temperature and the frequency and severity of hypoxic events. In this study, we explore the differences in hypoxia-transcriptional response between two populations of eastern oysters with known differences in hypoxia tolerance at three time points over the course of a 5-day hypoxia treatment. We identified sets of genes involved in the hypoxia response and found differences in both the timing and baseline expression of hypoxia-responsive genes between tolerant and sensitive populations, consistent with a scenario of local adaptation. Analysis of differential gene expression between the two populations and conditions revealed two gene modules with higher baseline expression of hypoxia-sensitive genes in the more hypoxia tolerant population. Key GO terms for genes corresponding to differences between populations include DNA repair, ribosome biogenesis, and ribonucleotide binding. Our results imply that differences in hypoxia tolerance between populations could be due to genetic frontloading of hypoxia response pathways in the more tolerant population.

The effect of fluvial avulsion on the Holocene chronostratigraphic record and the agricultural signal of the world's largest coastal lagoonal system - A.S.P. Avila; S.R. Bottezini; D. Diniz; C. Bueno; L. Perez; G. Martínez de la Escalera; C. Piccini; A. Leonhardt; F. Garcia-Rodriguez; J. Weschenfelder (Science of The Total Environment, 2024)

First Record of Conotrachelus quadrilineatus Champion, 1904 (Coleoptera: Curculionidae: Molytinae) Damaging Beans in South America - Daniel A. Baron-Ortiz; Fredy A. Rodriguez-Cruz; Oscar F. Santos-Amaya (Neotropical Entomology, 2024)
Common bean ( Phaseolus vulgaris L.) is the most important legume used for direct human consumption in Latin America, with an increasing expansion of cultivated areas in recent years. Here, we report the first occurrence of Conotrachelus quadrilineatus Champion, 1904 (Coleoptera: Curculionidae: Molytinae) feeding on bean in South America. Larvae and adults of C. quadrilineatus were observed during the first half of 2022, severely affecting the plantations of 20 bean farmers in the municipality of Garcia-Rovira, Santander Colombia. It is necessary to describe and quantify the damage of C. quadrilineatus in bean crops, as well as to study its bioecology.

"Effects of floating aquatic vegetation and canal sediment on phosphorus in drainage discharges in agricultural canals: A case study in the everglades agricultural area, Florida" - Mohsen Tootoonchi; Anne E. Sexton; Jennifer A. Cooper; Andres F. Rodriguez; Maryory Orton; Timothy A. Lang; Samira H. Daroub (Water Research, 2024)

Impact of a water restriction on the summer climatic benefits of trees inside an outdoor street canyon scale model - J. Thierry; S. Herpin; R. Levi; D. Canonne; S. Demotes-Mainard; P. Cannavo; D. Lemesle; L. Brialix; F. Rodriguez; P.E. Bournet (Building and Environment, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Sediment analysis and water quality assessment in the Pixquiac basin: drinking water supply of Xalapa city (Veracruz, Mexico) - M. C. Dupont; E. Martinez-Tavera; P. F. Rodriguez-Espinosa; A. G. Hernandez-Ramirez; P. Guadarrama Guzmán (Environmental Monitoring and Assessment, 2024)

Environmental performance analysis of coated austenitic steels for their use in supercritical steam turbines - M. Baranda; C. Mayo; R. Diaz; R. Rodriguez; F. J. Pérez (Clean Technologies and Environmental Policy, 2024)

Impact of Tissue Damage and Hemodynamics on Restenosis Following Percutaneous Transluminal Angioplasty: A Patient-Specific Multiscale Model - Anna Corti; Matilde Marradi; Cemre Çelikbudak Orhon; Francesca Boccafoschi; Philippe Büchler; Jose F. Rodriguez Matas; Claudio Chiastra (Annals of Biomedical Engineering, 2024)
Multiscale agent-based modeling frameworks have recently emerged as promising mechanobiological models to capture the interplay between biomechanical forces, cellular behavior, and molecular pathways underlying restenosis following percutaneous transluminal angioplasty (PTA). However, their applications are mainly limited to idealized scenarios. Herein, a multiscale agent-based modeling framework for investigating restenosis following PTA in a patient-specific superficial femoral artery (SFA) is proposed. The framework replicates the 2-month arterial wall remodeling in response to the PTA-induced injury and altered hemodynamics, by combining three modules: (i) the PTA module, consisting in a finite element structural mechanics simulation of PTA, featuring anisotropic hyperelastic material models coupled with a damage formulation for fibrous soft tissue and the element deletion strategy, providing the arterial wall damage and post-intervention configuration, (ii) the hemodynamics module, quantifying the post-intervention hemodynamics through computational fluid dynamics simulations, and (iii) the tissue remodeling module, based on an agent-based model of cellular dynamics. Two scenarios were explored, considering balloon expansion diameters of 5.2 and 6.2 mm. The framework captured PTA-induced arterial tissue lacerations and the post-PTA arterial wall remodeling. This remodeling process involved rapid cellular migration to the PTA-damaged regions, exacerbated cell proliferation and extracellular matrix production, resulting in lumen area reduction up to 1-month follow-up. After this initial reduction, the growth stabilized, due to the resolution of the inflammatory state and changes in hemodynamics. The similarity of the obtained results to clinical observations in treated SFAs suggests the potential of the framework for capturing patient-specific mechanobiological events occurring after PTA intervention.

Mn and Co decorated biomorphic ceria fiber catalysts for soot and benzene total oxidation. - M. Rodriguez; F. Hanon; F. Devred; E.M. Gaigneaux; E.E. Miró; V.G. Milt (Chemosphere, 2024)

Pioneering minimum liquid discharge desalination: A pilot study in Lampedusa Island - C. Morgante; F. Vassallo; C. Cassaro; G. Virruso; D. Diamantidou; N. Van Linden; A. Trezzi; C. Xenogianni; R. Ktori; M. Rodriguez; G. Scelfo; S. Randazzo; et al. (Desalination, 2024)

The imprint of coevolving semi-arid landscapes, soil, and vegetation on soil moisture and vegetation variability - Ankur Srivastava; Omer Yetemen; Jose F. Rodriguez; Nikul Kumari; Patricia M. Saco (CATENA, 2024)

Population genetics and demography of the endemic mouse species of Cyprus, Mus cypriacus - Emilie A. Hardouin; Francesca Riccioli; Demetra Andreou; Miguel Baltazar-Soares; Marin Cvitanović; Nathan F. Williams; Pascale Chevret; Sabrina Renaud; Oxala García-Rodriguez; Eleftherios Hadjisterkotis; Despoina Miltiadou; Miloš Macholán; et al. (Mammalian Biology, 2024)
Mus cypriacus is one of three small palaeoendemic mammals that have survived the Mediterranean islands’ anthropization. This species, endemic to Cyprus, was described in 2006 and stands out as one of the last mammal species to have been discovered in Europe. Despite scarce data on its genetics, ecology, and life-history traits, Mus cypriacus is assessed as Least Concern LC in the IUCN Red List, partly due to its morphological similarity with the sympatric house mouse that prevented earlier identification. Our study uses mitochondrial and microsatellite markers to investigate this small rodent's population genetic structure and diversity. Our analysis did not identify any population genetic structure and suggested a high genetic diversity across Cyprus. When inferring habitat preference using sample locations, it appeared that M. cypriacus utilizes a diverse variety of habitats, covering more than 80% of the island. Although these results are encouraging for the conservation status of the species, they still need to be cautiously applied as potential threats may arise due to increasing habitat destruction and changes in land use. Consequently, our encouraging results should be applied judiciously. Additional ecological data are urgently needed to gain a more comprehensive understanding of this inconspicuous endemic species.

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Trophic ecology of sympatric sea turtles in the tropical Atlantic coast of Brazil - Moises F. Bezerra; Cesar A. Barrios-Rodriguez; Carlos E. Rezende; Melania C. López-Castro; Luiz D. Lacerda (Marine Environmental Research, 2024)

Considerations for the development of guidance on dose level selection for developmental and reproductive toxicity studies - R.W. Lewis; A.K. Andrus; J. Arroyo; S. Brescia; P.A. Botham; M. Corvaro; G.P. Daston; T. Hofmann; C. Rodriguez; F. Sewell; B. van Ravenzwaay; K. Wiench; et al. (Regulatory Toxicology and Pharmacology, 2024)

Holocene organic matter composition in relation to relative sea level stands and associated morphometric changes of a lagoonal system - V. Carvalho; L. Gonzalez; C. Bueno; C. Segura; S.R. Bottezini; A. Leonhardt; D. Diniz; P. Dentzien-Dias; L. Perez; H. Evangelista; M.V. Licínio; H. Inda; et al. (Marine Geology, 2024)

Welfare of rainbow trout at slaughter: Integrating behavioural, physiological, proteomic and quality indicators and testing a novel fast-chill stunning method - João L. Saraiva; Filippo Faccenda; María J. Cabrera-Álvarez; Michele Povinelli; Peter C. Hubbard; Marco Cerqueira; Ana Paula Farinha; Giulia Secci; Maria Vittoria Tignani; Lina F. Pulido Rodriguez; Giuliana Parisi (Aquaculture, 2024)

Assessment of gill microbiome of two strains of Atlantic salmon reared in flowthrough and recirculation hatcheries and following seawater transfer - Petra R. Quezada-Rodriguez; Jamie Downes; Fintan Egan; Richard S. Taylor; Samantha White; Aisling Brenan; Megan L. Rigby; Barbara F. Nowak; James W. Wynne; Neil M. Ruane (Aquaculture, 2024)

Impact of calibrating a low-cost capacitance-based soil moisture sensor on AquaCrop model performance - Soham Adla; Felix Bruckmaier; Leonardo F. Arias-Rodriguez; Shivam Tripathi; Saket Pande; Markus Disse (Journal of Environmental Management, 2024)

A new data analysis approach for an AgNPs-modified impedimetric bioelectronic tongue for dairy analysis - C. Perez-Gonzalez; C. Salvo-Comino; F. Martin-Pedrosa; M.L. Rodriguez-Mendez; C. Garcia-Cabezon (Food Control, 2024)

Embryo-maternal communication mediated by extracellular vesicles in the early stages of embryonic development is modified by in vitro conditions - C. Aguilera; Y.S. Wong; M.A. Gutierrez-Reinoso; A.E. Velásquez; B. Melo-Báez; J. Cabezas; D. Caamaño; F. Navarrete; F.O. Castro; L.l. Rodriguez-Alvarez (Theriogenology, 2024)

Regional differences in Hg contents in the liver and muscle of the green turtle (Chelonia mydas) from three foraging grounds in Northeast Brazil - Paul Verzele; César B. Rodriguez; Moisés F. Bezerra; Luiz D. Lacerda (Environmental Science and Pollution Research, 2023)

Alkaline pretreatment of a polymetallic sulfide (Fe-Pb-Mn) ore containing silver increases the efficiency of cyanidation by decreasing elemental sulfur content and by exposing sulfide surfaces - Gonzalo Larrabure; Dhamelyz Silva-Quiñones; Andrew V. Teplyakov; Juan Carlos F. Rodriguez-Reyes (Minerals Engineering, 2023)

Analysis of factors controlling maize yield response to hairy vetch and to nitrogen fertilization after hairy vetch - W.D. Carciochi; F. Cafaro La Menza; C. Crespo; G. Dominguez; M.P. Rodriguez; N.I. Reussi Calvo; N. Wyngaard; H.R. Sainz Rozas; G. Studdert; P. Barbieri (Field Crops Research, 2023)

Human milk: From complex tailored nutrition to bioactive impact on child cognition and behavior - Carolina de Weerth; Anna-Katariina Aatsinki; Meghan B. Azad; Frank F. Bartol; Lars Bode; Maria Carmen Collado; Amanda M. Dettmer; Catherine J. Field; Meagan Guilfoyle; Katie Hinde; Aniko Korosi; Hellen Lustermans; et al. (Critical Reviews in Food Science and Nutrition, 2023)

First evidence of environmental bioaccumulation of pharmaceuticals on adult native anurans (Rhinella arenarum) from Argentina - C. Salgado Costa; F. Bahl; G.S. Natale; T.M. Mac Loughlin; D.J.G. Marino; A. Venturino; S. Rodriguez-Mozaz; L.H.M.L.M. Santos (Environmental Pollution, 2023)

Cu(II)-acylhydrazone complex, a potent and selective antitumor agent against human osteosarcoma: Mechanism of action studies over in vitro and in vivo models - Lucia M. Balsa; Luisina M. Solernó; Maria R. Rodriguez; Beatriz S. Parajón-Costa; Ana C. Gonzalez-Baró; Daniel F. Alonso; Juan Garona; Ignacio E. León (Chemico-Biological Interactions, 2023)

Host manipulation by parasites through the lens of Niche Construction Theory - Lucas Rodriguez Forti; Judit K. Szabo; Hilton F. Japyassú (Behavioural Processes, 2023)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Effect of intra-uterine infusion of prostaglandin E1 on equine serum level and intra-ovulatory interval - Claire E Card; Mariana Diel de Amorim; Mike Byron; Julia Quental-Caribe; Maria F Lopez-Rodriguez (Journal of Equine Veterinary Science, 2023)

Dry-spun carbon nanotube ultrafiltration membranes tailored by anti-viral metal oxide coatings for human coronavirus 229E capture in water - Ahmed O. Rashed; Chi Huynh; Andrea Merenda; Julio Rodriguez-Andres; Lingxue Kong; Takeshi Kondo; Joselito M. Razal; Ludovic F. Dumée (Journal of Environmental Chemical Engineering, 2023)

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

Emerging themes and future directions in watershed resilience research - Fernando Miralles-Wilhelm; John H. Matthews; Nathan Karres; Robin Abell; James Dalton; Shi-Teng Kang; Junguo Liu; Romain Maendly; Nathanial Matthews; Robert McDonald; Raúl Muñoz-Castillo; Boris F. Ochoa-Tocachi; et al. (Water Security, 2023)

Kisspeptin as potential biomarker of environmental chemical mixture effect on reproductive hormone profile: A pilot study in adolescent males - Andrea Rodriguez-Carrillo; Sylvie Remy; Shereen Cynthia D'Cruz; Elena Salamanca-Fernandez; Fernando Gil; Pablo Olmedo; Vicente Mustieles; Fernando Vela-Soria; Kirsten Baken; Nicolás Olea; Fátima Smagulova; Mariana F. Fernandez; et al. (Science of The Total Environment, 2023)

Holistic Assessment of Calcium Fertilization in Potato: Diagnostic, Productivity, and Tuber Quality - C. M. Giletto; M. Kloster Erreguerrena; P. Ceroli; W. Carciochi; S. E. Silva; S. Rodriguez; F. Salvagiotti; N. I. Reussi Calvo (Journal of Soil Science and Plant Nutrition, 2023)

Adapting to climate change on desert rangelands: A multi-site comparison of grazing behavior plasticity of heritage and improved beef cattle - Andres F. Cibils; Rick E. Estell; Sheri Spiegal; Shelemia Nyamuryekung'e; Matthew M. McIntosh; Danielle M. Duni; Oscar A. Herrera Conegliano; Felipe A. Rodriguez Almeida; Octavio Roacho Estrada; Lisandro J. Blanco; Michael C. Duniway; Santiago A. Utsumi; et al. (Journal of Arid Environments, 2023)

Consumption of Foods Away from Home Is Associated with Lower Diet Quality Among Adults Living in Puerto Rico - Nayla Bezares; Amanda C. McClain; Martha Tamez; Jose F. Rodriguez-Orengo; Katherine L. Tucker; Josiemer Mattei (Journal of the Academy of Nutrition and Dietetics, 2023)

Correction to: Multiple Alr genes exhibit allorecognition-associated variation in the colonial cnidarian Hydractinia - Henry Rodriguez-Valbuena; Andrea Gonzalez-Muñoz; Luis F. Cadavid (Immunogenetics, 2022)

Multiple Alr genes exhibit allorecognition-associated variation in the colonial cnidarian Hydractinia - Henry Rodriguez-Valbuena; Andrea Gonzalez-Muñoz; Luis F. Cadavid (Immunogenetics, 2022)

Prevalence of epitheliocystis in freshwater Atlantic salmon reared in flow‐through and recirculation aquaculture systems - Petra R. Quezada‐Rodriguez; Richard S. Taylor; Jamie Downes; Fintan Egan; Samantha White; Aisling Brenan; Megan Rigby; Barbara F. Nowak; Neil M. Ruane; James W. Wynne (Journal of Fish Diseases, 2022)
Epitheliocystis, an intracellular bacterial infection in the gills and skin epithelium, has been frequently reported in Atlantic salmon ( Salmo salar ) during freshwater production in a number of countries. This study describes the prevalence and intensity of a natural epitheliocystis infection present in the gills of two strains of Atlantic salmon reared in either a flow‐through (FT) or a recirculation aquaculture system (RAS) in Ireland. Repeated sampling of gills prior to and throughout seawater transfer, histology and quantitative real‐time PCR were used to determine infection prevalence and intensity. Despite no clinical gill disease, and minor histopathological changes, epitheliocystis lesions were identified in histology at all time points. Specific PCR confirmed the presence of Candidatus Clavichlamydia salmonicola in both strains and its number of copies was correlated with intensity of epitheliocystis lesions. A significant interaction between hatchery system and fish strain on the prevalence and intensity of gill epitheliocystis was found both using histological and molecular methods. Specifically, fish from FT had higher prevalence and intensity than RAS reared fish and within FT, the Irish cohort were more affected than Icelandic.

An overview of ionic liquid degradation by advanced oxidation processes - Ismael F. Mena; Elena Diaz; Juan J. Rodriguez; Angel F. Mohedano (Critical Reviews in Environmental Science and Technology, 2022)

The Colombian geochronological database (CGD) - Andres F. Rodriguez-Corcho; Yamirka Rojas-Agramonte; Johana A. Barrera-Gonzalez; Maria P. Marroquin-Gomez; Sarah Bonilla-Correa; David Izquierdo-Camacho; Sofia M. Delgado-Balaguera; David Cartwright-Buitrago; Maria D. Muñoz-Granados; William G. Carantón-Mateus; Alejandro Corrales-García; Andrés F. Laverde-Martinez; et al. (International Geology Review, 2022)

Coral‐bleaching responses to climate change across biological scales - Robert van Woesik; Tom Shlesinger; Andréa G. Grottoli; Rob J. Toonen; Rebecca Vega Thurber; Mark E. Warner; Ann Marie Hulver; Leila Chapron; Rowan H. McLachlan; Rebecca Albright; Eric Crandall; Thomas M. DeCarlo; et al. (Global Change Biology, 2022)
The global impacts of climate change are evident in every marine ecosystem. On coral reefs, mass coral bleaching and mortality have emerged as ubiquitous responses to ocean warming, yet one of the greatest challenges of this epiphenomenon is linking information across scientific disciplines and spatial and temporal scales. Here we review some of the seminal and recent coral‐bleaching discoveries from an ecological, physiological, and molecular perspective. We also evaluate which data and processes can improve predictive models and provide a conceptual framework that integrates measurements across biological scales. Taking an integrative approach across biological and spatial scales, using for example hierarchical models to estimate major coral‐reef processes, will not only rapidly advance coral‐reef science but will also provide necessary information to guide decision‐making and conservation efforts. To conserve reefs, we encourage implementing mesoscale sanctuaries (thousands of km 2 ) that transcend national boundaries. Such networks of protected reefs will provide reef connectivity, through larval dispersal that transverse thermal environments, and genotypic repositories that may become essential units of selection for environmentally diverse locations. Together, multinational networks may be the best chance corals have to persist through climate change, while humanity struggles to reduce emissions of greenhouse gases to net zero.

Enacting boundaries or building bridges? Language and engagement in food-energy-water systems science - Valoree S. Gagnon; Chelsea Schelly; William Lytle; Andrew Kliskey; Virginia H. Dale; Anna-Maria Marshall; Luis F. Rodriguez; Paula Williams; Michael Waasegiizhig Price; Elizabeth A. Redd; Margaret A. Noodin (Socio-Ecological Practice Research, 2022)
Scientific study of issues at the nexus of food–energy–water systems (FEWS) requires grappling with multifaceted, “wicked” problems. FEWS involve interactions occurring directly and indirectly across complex and overlapping spatial and temporal scales; they are also imbued with diverse and sometimes conflicting meanings for the human and more-than-human beings that live within them. In this paper, we consider the role of language in the dynamics of boundary work, recognizing that the language often used in stakeholder and community engagement intended to address FEWS science and decision-making constructs boundaries and limits diverse and inclusive participation. In contrast, some language systems provide opportunities to build bridges rather than boundaries in engagement. Based on our experiences with engagement in FEWS science and with Indigenous knowledges and languages, we consider examples of the role of language in reflecting worldviews, values, practices, and interactions in FEWS science and engagement. We particularly focus on Indigenous knowledges from Anishinaabe and the language of Anishinaabemowin, contrasting languages of boundaries and bridges through concrete examples. These examples are used to unpack the argument of this work, which is that scientific research aiming to engage FEWS issues in working landscapes requires grappling with embedded, practical understandings. This perspective demonstrates the importance of grappling with the role of language in creating boundaries or bridges, while recognizing that training in engagement may not critically reflect on the role of language in limiting diversity and inclusivity in engagement efforts. Leaving this reflexive consideration of language unexamined may unknowingly perpetuate boundaries rather than building bridges, thus limiting the effectiveness of engagement that is intended to address wicked problems in working landscapes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Recent Reports on Redox Stress-Induced Mitochondrial DNA Variations, Neuroglial Interactions, and NMDA Receptor System in Pathophysiology of Schizophrenia - Narasimha M. Beeraka; Marco F. Avila-Rodriguez; Gjumrakch Aliev (Molecular Neurobiology, 2022)

Degradation of dibutyl phthalate by Paenarthrobacter sp. Shss isolated from Saravan landfill, Hyrcanian Forests, Iran - S. Shariati; C. Ebenau-Jehle; A. A. Pourbabaee; H. A. Alikhani; M. Rodriguez-Franco; M. Agne; M. Jacoby; R. Geiger; F. Shariati; M. Boll (Biodegradation, 2022)
Phthalic acid esters are predominantly used as plasticizers and are industrially produced on the million ton scale per year. They exhibit endocrine-disrupting, carcinogenic, teratogenic, and mutagenic effects on wildlife and humans. For this reason, biodegradation, the major process of phthalic acid ester elimination from the environment, is of global importance. Here, we studied bacterial phthalic acid ester degradation at Saravan landfill in Hyrcanian Forests, Iran, an active disposal site with 800 tons of solid waste input per day. A di- n -butyl phthalate degrading enrichment culture was established from which Paenarthrobacter sp. strain Shss was isolated. This strain efficiently degraded 1 g L –1 di- n -butyl phthalate within 15 h with a doubling time of 5 h. In addition, dimethyl phthalate, diethyl phthalate, mono butyl phthalate, and phthalic acid where degraded to CO 2 , whereas diethyl hexyl phthalate did not serve as a substrate. During the biodegradation of di- n -butyl phthalate, mono- n -butyl phthalate was identified in culture supernatants by ultra-performance liquid chromatography coupled to electrospray ionization quadrupole time-of-flight mass spectrometry. In vitro assays identified two cellular esterase activities that converted di- n -butyl phthalate to mono- n -butyl phthalate, and the latter to phthalic acid, respectively. Our findings identified Paenarthrobacter sp. Shss amongst the most efficient phthalic acid esters degrading bacteria known, that possibly plays an important role in di- n -butyl phthalate elimination at a highly phthalic acid esters contaminated landfill.

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

Cryptic speciation in Orbilia xanthostigma and O. leucostigma (Orbiliomycetes): an aggregate with worldwide distribution - Hans-Otto Baral; Peter Johnston; Luis Quijada; Rosanne Healy; Donald H. Pfister; Katherine F. LoBuglio; Valentina Rodriguez; Evi Weber (Mycological Progress, 2021)

NGS and phenotypic ontology-based approaches increase the diagnostic yield in syndromic retinal diseases - I. Perea-Romero; F. Blanco-Kelly; I. Sanchez-Navarro; I. Lorda-Sanchez; S. Tahsin-Swafiri; A. Avila-Fernandez; I. Martin-Merida; M. J. Trujillo-Tiebas; R. Lopez-Rodriguez; M. Rodriguez de Alba; I. F. Iancu; R. Romero; et al. (Human Genetics, 2021)
Syndromic retinal diseases (SRDs) are a group of complex inherited systemic disorders, with challenging molecular underpinnings and clinical management. Our main goal is to improve clinical and molecular SRDs diagnosis, by applying a structured phenotypic ontology and next-generation sequencing (NGS)-based pipelines. A prospective and retrospective cohort study was performed on 100 probands with an a priori diagnosis of non-Usher SRDs, using available clinical data, including Human Phenotype Ontology annotation, and further classification into seven clinical categories (ciliopathies, specific syndromes and five others). Retrospective molecular diagnosis was assessed using different molecular and bioinformatic methods depending on availability. Subsequently, uncharacterized probands were prospectively screened using other NGS approaches to extend the number of analyzed genes. After phenotypic classification, ciliopathies were the most common SRD (35%). A global characterization rate of 52% was obtained, with six cases incompletely characterized for a gene that partially explained the phenotype. An improved characterization rate was achieved addressing prospective cases (83%) and well-recognizable syndrome (62%) subgroups. The 27% of the fully characterized cases were reclassified into a different clinical category after identification of the disease-causing gene. Clinical-exome sequencing is the most appropriate first-tier approach for prospective cases, whereas whole-exome sequencing and bioinformatic reanalysis increases the diagnosis of uncharacterized retrospective cases to 45%, mostly those with unspecific symptoms. Our study describes a comprehensive approach to SRDs in daily clinical practice and the importance of thorough clinical assessment and selection of the most appropriate molecular test to be used to solve these complex cases and elucidate novel associations.

Predicting Atrial Fibrillation with High Risk of Embolization with Atrial Strain and NT-proBNP - Jorge Pagola; Jesus Juega; Jaume Francisco-Pascual; Alejandro Bustamante; Anna Penalba; Elena Pala; Maite Rodriguez; Mercedes De Lera-Alfonso; Juan F. Arenillas; Juan Antonio Cabezas; Francisco Moniche; Reyes de Torres; et al. (Translational Stroke Research, 2021)

Sulfur isotope fractionations constrain the biological cycling of dimethylsulfoniopropionate in the upper ocean - Daniela Osorio‐Rodriguez; Manuel Razo‐Mejia; Nathan F. Dalleska; Alex L. Sessions; Victoria J. Orphan; Jess F. Adkins (Limnology and Oceanography, 2021)
The rapid turnover of dimethylsulfoniopropionate (DMSP), likely the most relevant dissolved organic sulfur compound in the surface ocean, makes it pivotal to understand the cycling of organic sulfur. Dimethylsulfoniopropionate is mainly synthesized by phytoplankton, and it can be utilized as carbon and sulfur sources by marine bacteria or cleaved by bacteria or algae to produce the volatile compound dimethylsulfide (DMS), involved in the formation of sulfate aerosols. The fluxes between the consumption (i.e., demethylation) and cleavage pathways are thought to depend on community interactions and their sulfur demand. However, a quantitative assessment of the sulfur partitioning between each of these pathways is still missing. Here, we report for the first time the sulfur isotope fractionations by enzymes involved in DMSP degradation with different catalytic mechanisms, expressed heterologously in Escherichia coli . We show that the residual DMSP from the demethylation pathway is 2.7‰ enriched in δ 34 S relative to the initial DMSP, and that the fractionation factor ( 34 ε ) of the cleavage pathways varies between −1 and −9‰. The incorporation of these fractionation factors into mass balance calculations constrains the biological fates of DMSP in seawater, supports the notion that demethylation dominates over cleavage in marine environments, and could be used as a proxy for the dominant pathways of degradation of DMSP by marine microbial communities.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

An Economic Perspective on Policies to Save the Vaquita: Conservation Actions, Wildlife Trafficking, and the Structure of Incentives - Enrique Sanjurjo-Rivera; Sarah L. Mesnick; Sara Ávila-Forcada; Oriana Poindexter; Rebecca Lent; Vanda Felbab-Brown; Andrés M. Cisneros-Montemayor; Dale Squires; U. Rashid Sumaila; Gordon Munro; Rafael Ortiz-Rodriguez; Ramses Rodriguez; et al. (Frontiers in Marine Science, 2021)
The Upper Gulf of California is a diverse and highly productive ecosystem supporting some of the most important fisheries in Mexico, yet a history of weak fisheries management and illegal fishing threaten the area’s biodiversity and undermine human well-being in the communities along its shores. The vaquita ( Phocoena sinus) is endemic to these waters and is on the brink of extinction due to incidental entanglement in gillnets used by small-scale fishers. The resurgence of an illegal gillnet fishery for totoaba ( Totoaba macdonaldi ), whose swim bladders are highly prized in Hong Kong and continental China, has accelerated the steep decline of the vaquita population. Vaquita is one of a growing number of cases linking illegal wildlife trade, organized crime, and biodiversity decline. This paper provides a summary of key reflections of a panel of fisheries economists gathered at the ninth forum of the North American Association of Fisheries Economists (NAAFE) to evaluate the policies implemented in the Upper Gulf through an economic lens and updated to reflect more recent developments. The panel recognized that poor fisheries management, lack of effective enforcement, distant demand for an illegal product, corruption, and few viable economic alternatives confound efforts to address vaquita bycatch. The complexity of these problems requires a holistic, multidisciplinary approach, combining top-down, direct regulation and bottom-up, participatory and incentive-based instruments. Addressing chronic deficiencies in enforcement, particularly in the very small area where the remaining vaquitas are found, is crucial to prevent imminent extinction. Equally crucial are sustained actions to support legal fishers able to make a good living – with a direct stake in healthy marine ecosystems – as key components of policies to address bycatch and reduce wildlife trafficking. The situation in the Upper Gulf of California is dire, yet similar threats to other marine mammals and wildlife trafficked species may benefit from the experience of the vaquita.

Correction to: Summer phyto‑ and bacterioplankton communities during low and high productivity scenarios in the Western Antarctic Peninsula - Sebastián Fuentes; José Ignacio Arroyo; Susana Rodriguez‑Marconi; Italo Masotti; Tomás Alarcon‑Schumacher; Martin F. Polz; Nicole Trefault; Rodrigo De la Iglesia; Beatriz Díez (Polar Biology, 2021)

Nutritional and ecotoxicological aspects of the acidotolerant alga Keratococcus rhaphidioides (Chlorophyta): a potential candidate for algal mediated bioremediation of extremely acidic waters - J. M. Cabrera; S. S. Schultz; G. D. Baffico; M. C. Rodriguez; F. L. Pedrozo; M. M. Diaz (Journal of Applied Phycology, 2021)

An intrapopulational study of organic compounds and biomechanical properties of the shell of the Antarctic bivalve Laternula elliptica (P. P. King, 1832) at King George Island - M. Roberto García-Huidobro; María Josefina Poupin; Cristóbal Urrutia; Alejandro B. Rodriguez-Navarro; Christian Grenier; Juan F. Vivanco; Laura Ramajo; Isabel Benjumeda; Nelson A. Lagos; Marco A. Lardies (Polar Biology, 2021)

Comparison of real and simulated lava flows in the Holocene volcanism of Gran Canaria (Canary Islands, Spain) with Q-LavHA: contribution to volcanic hazard management - A. Rodriguez-Gonzalez; M. Aulinas; S. Mossoux; F. J. Perez-Torrado; J. L. Fernandez-Turiel; M. Cabrera; C. Prieto-Torrell (Natural Hazards, 2021)

Managing groundwater supplies subject to drought: perspectives on current status and future priorities from England (UK) - M. J. Ascott; J. P. Bloomfield; I. Karapanos; C. R. Jackson; R. S. Ward; A. B. McBride; B. Dobson; N. Kieboom; I. P. Holman; A. F. Van Loon; E. J. Crane; B. Brauns; et al. (Hydrogeology Journal, 2021)
Effective management of groundwater resources during drought is essential. How is groundwater currently managed during droughts, and in the face of environmental change, what should be the future priorities? Four themes are explored, from the perspective of groundwater management in England (UK): (1) integration of drought definitions; (2) enhanced fundamental monitoring; (3) integrated modelling of groundwater in the water cycle; and (4) better information sharing. Whilst these themes are considered in the context of England, globally, they are relevant wherever groundwater is affected by drought.

The current situation and future perspectives of Quercus ilex and Pinus halepensis afforestation on agricultural land in Spain under climate change scenarios - L. Quinto; Rafael M. Navarro-Cerrillo; Guillermo Palacios-Rodriguez; F. Ruiz-Gómez; J. Duque-Lazo (New Forests, 2021)

Umbilical cord: an allogenic tissue for potential treatment of COVID-19 - Hugo C. Rodriguez; Manu Gupta; Emilio Cavazos-Escobar; Saadiq F. El-Amin; Ashim Gupta (Human Cell, 2021)

Tacit working models of human behavioural change II: Farmers’ folk theories of conservation programme design - M. Root-Bernstein; A. Bondoux; M. Guerrero-Gatica; F. Zorondo-Rodriguez (Ambio, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

The Effect of Short-Term Physical Activity on the Oxidative Stress in Rats with Different Stress Resistance Profiles in Cerebral Hypoperfusion - Vladimir V. Chrishtop; Irina K. Tomilova; Tatiana A. Rumyantseva; Elizaveta V. Mikhaylenko; Marco F. Avila-Rodriguez; Liudmila M. Mikhaleva; Vladimir N. Nikolenko; Siva G. Somasundaram; Cecil E. Kirkland; Sergey O. Bachurin; Gjumrakch Aliev (Molecular Neurobiology, 2020)

Three-dimensional regional bi-ventricular shape remodeling is associated with exercise capacity in endurance athletes - G. Bernardino; M. Sanz de la Garza; B. Domenech-Ximenos; S. Prat-Gonzàlez; R. J. Perea; I. Blanco; F. Burgos; A. Sepulveda-Martinez; M. Rodriguez-Lopez; F. Crispi; C. Butakoff; M. A. González Ballester; et al. (European Journal of Applied Physiology, 2020)

A Metabolic Intravascular Platform to Study FDG Uptake in Vascular Injury - F. Franchi; M. Olthoff; J. Krier; C. Noble; M. Al-Hijji; V. Ramaswamy; T. Witt; M. Burke; M. Benscoter; A. Lerman; G. S. Sandhu; M. Rodriguez-Porcel (Cardiovascular Engineering and Technology, 2020)

A new livebearing fish of the genus Limia (Cyprinodontiformes: Poeciliidae) from Lake Miragoane, Haiti - Rodet Rodriguez‐Silva; Pablo F. Weaver (Journal of Fish Biology, 2020)
Limia islai , a new species of livebearing fish, is described from Lake Miragoane in south‐western Haiti on Hispaniola. The new species has a conspicuous barred pattern consisting of several (4–12) black bars along the body, ray 4p serrae of the gonopodium in males with 10 segments and origin of dorsal fin in females slightly behind the origin of the anal fin. Although the new species colour pattern is similar to that of the humpbacked limia Limia nigrofasciata Regan 1913, L. islai sp. nov. has exclusive morphological features, such as slender body, lack of hump anterior to dorsal fin in males and presence of specific features in the gonopodial suspensory, which allow an unambiguous diagnosis from L. nigrofasciata . L. islai further differs from L. nigrofasciata in reproductive behaviour since L. islai males rely on sneak copulations and gonopodial thrusting, whereas L. nigrofasciata display an elaborate courtship behaviour. The new species is also genetically distinct in both nuclear (Rh, Myh6) and mitochondrial (12S, ND2, D‐loop, Cytb) genes from other species in the genus showing reciprocal monophyly. The description of this new Limia species from Lake Miragoane confirms this lake as an important centre of endemism for the genus, with a total of eight endemic species described so far.

Sexual recombination within the “Kranich” race of the yellow rust fungus Puccinia striiformis f.sp. tritici on Berberis vulgaris - J. Rodriguez-Algaba; M. S. Hovmøller; A. F. Justesen (European Journal of Plant Pathology, 2020)

Adenovirus-Mediated Transduction of Insulin-Like Growth Factor 1 Protects Hippocampal Neurons from the Toxicity of Aβ Oligomers and Prevents Memory Loss in an Alzheimer Mouse Model - Maria Clara Selles; Juliana T. S. Fortuna; Maria F. Zappa-Villar; Yasmin P. R. de Faria; Amanda S. Souza; Claudia K. Suemoto; Renata E. P. Leite; Roberta D. Rodriguez; Lea T. Grinberg; Paula C. Reggiani; Sergio T. Ferreira (Molecular Neurobiology, 2020)

Adsorption of Diclofenac from Aqueous Solution onto Carbon Xerogels: Effect of Synthesis Conditions and Presence of Bacteria - A. I. Moral-Rodriguez; R. Leyva-Ramos; F. Carrasco-Marín; M. I. Bautista-Toledo; A. F. Pérez-Cadenas (Water, Air, & Soil Pollution, 2020)

A comparison of regional brain volumes and white matter connectivity in subjects with stimulant induced psychosis versus schizophrenia - Peter D. Alexander; Kristina M. Gicas; Alex Cheng; Donna J. Lang; Ric M. Procyshyn; Alexandra T. Vertinsky; William J. Panenka; Allen E. Thornton; Alexander Rauscher; Jamie Y. X. Wong; Tasha Chan; Andrea A. Jones; et al. (Psychopharmacology, 2019)

Metabolomic profile of cacao cell suspensions growing in blue light/dark conditions with potential in food biotechnology - Adriana M. Gallego; Luisa F. Rojas; Héctor A. Rodriguez; Conrado Mora; Lucía Atehortúa; Aura I. Urrea; Mark J. Guiltinan; Siela N. Maximova; Emmanuel Gaquerel; Martha Zuluaga; Natalia Pabón-Mora (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Availability of lead in agricultural soils amended with compost of biosolid with wood shavings and yard trimmings - Gisele V. Ferreyroa; Carolina Vergara Cid; Romina A. Verdenelli; María F. Dominchin; José M. Meriles; María L. Pignata; Judith H. Rodriguez (Environmental Science and Pollution Research, 2019)

Phylogenomics of Enterococcus faecalis from wild birds: new insights into host‐associated differences in core and accessory genomes of the species - Ricardo León‐Sampedro; Rosa del Campo; Mercedes Rodriguez‐Baños; Val F. Lanza; María José Pozuelo; Carlos Francés‐Cuesta; Ana P. Tedim; Ana R. Freitas; Carla Novais; Luísa Peixe; Rob J. L. Willems; Jukka Corander; et al. (Environmental Microbiology, 2019)
Summary Wild birds have been suggested to be reservoirs of antimicrobial resistant and/or pathogenic Enterococcus faecalis ( Efs ) strains, but the scarcity of studies and available sequences limit our understanding of the population structure of the species in these hosts. Here, we analysed the clonal and plasmid diversity of 97 Efs isolates from wild migratory birds. We found a high diversity, with most sequence types (STs) being firstly described here, while others were found in other hosts including some predominant in poultry. We found that pheromone‐responsive plasmids predominate in wild bird Efs while 35% of the isolates entirely lack plasmids. Then, to better understand the ecology of the species, the whole genome of fivestrains with known STs (ST82, ST170, ST16 and ST55) were sequenced and compared with all the Efs genomes available in public databases. Using several methods to analyse core and accessory genomes (AccNET, PLACNET, hierBAPS and PANINI), we detected differences in the accessory genome of some lineages (e.g. ST82) demonstrating specific associations with birds. Conversely, the genomes of other Efs lineages exhibited divergence in core and accessory genomes, reflecting different adaptive trajectories in various hosts. This pangenome divergence, horizontal gene transfer events and occasional epidemic peaks could explain the population structure of the species.

Bioethanol Production From Sugarcane Bagasse Hemicellulose Hydrolysate by Immobilized S. shehatae in a Fluidized Bed Fermenter Under Magnetic Field - Kelly J. Dussán; Oselys Rodriguez Justo; Victor Haber Perez; Geraldo F. David; Euripedes Garcia Silveira Junior; Silvio S. da Silva (BioEnergy Research, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Nutritional evaluation and productivity of supplemented sheep grazing in semiarid rangeland of northeastern Brazil - A. R. Araújo; N. M. Rodriguez; Marcos Cláudio Pinheiro Rogério; I. Borges; E. O. S. Saliba; S. A. Santos; R. C. F. F. Pompeu; F. E. P. Fernandes; J. P. Monteiro; J. P. Muir (Tropical Animal Health and Production, 2019)

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

The Neuronal Ischemic Tolerance Is Conditioned by the Tp53 Arg72Pro Polymorphism - Maria E. Ramos-Araque; Cristina Rodriguez; Rebeca Vecino; Elisa Cortijo Garcia; Mercedes de Lera Alfonso; Mercedes Sanchez Barba; Laura Colàs-Campàs; Francisco Purroy; Juan F. Arenillas; Angeles Almeida; Maria Delgado-Esteban (Translational Stroke Research, 2019)
Cerebral preconditioning (PC) confers endogenous brain protection after stroke. Ischemic stroke patients with a prior transient ischemic attack (TIA) may potentially be in a preconditioned state. Although PC has been associated with the activation of pro-survival signals, the mechanism by which preconditioning confers neuroprotection is not yet fully clarified. Recently, we have described that PC-mediated neuroprotection against ischemic insult is promoted by p53 destabilization, which is mediated by its main regulator MDM2. Moreover, we have previously described that the human Tp53 Arg72Pro single nucleotide polymorphism (SNP) controls susceptibility to ischemia-induced neuronal apoptosis and governs the functional outcome of patients after stroke. Here, we studied the contribution of the human Tp53 Arg72Pro SNP on PC-induced neuroprotection after ischemia. Our results showed that cortical neurons expressing the Pro72-p53 variant exhibited higher PC-mediated neuroprotection as compared with Arg72-p53 neurons. PC prevented ischemia-induced nuclear and cytosolic p53 stabilization in Pro72-p53 neurons. However, PC failed to prevent mitochondrial p53 stabilization, which occurs in Arg72-p53 neurons after ischemia. Furthermore, PC promoted neuroprotection against ischemia by controlling the p53/active caspase-3 pathway in Pro72-p53, but not in Arg72-p53 neurons. Finally, we found that good prognosis associated to TIA within 1 month prior to ischemic stroke was restricted to patients harboring the Pro72 allele. Our findings demonstrate that the Tp53 Arg72Pro SNP controls PC-promoted neuroprotection against a subsequent ischemic insult by modulating mitochondrial p53 stabilization and then modulates TIA-induced ischemic tolerance.

pH Variability Exacerbates Effects of Ocean Acidification on a Caribbean Crustose Coralline Alga - Maggie D. Johnson; Lucia M. Rodriguez Bravo; Shevonne E. O’Connor; Nicholas F. Varley; Andrew H. Altieri (Frontiers in Marine Science, 2019)

Serum P-glycoprotein level: a potential biomarker of DMARD failure in patients with rheumatoid arthritis - E. E. Perez-Guerrero; L. Gonzalez-Lopez; J. F. Muñoz-Valle; J. C. Vasquez-Jimenez; M. Ramirez-Villafaña; E. N. Sanchez-Rodriguez; S. R. Gutierrez-Ureña; S. Cerpa-Cruz; E. A. Aguilar-Chavez; E. G. Cardona-Muñoz; M. L. Vazquez-Villegas; A. M. Saldaña-Cruz; et al. (Inflammopharmacology, 2018)

Removal of imidazolium- and pyridinium-based ionic liquids by Fenton oxidation - Esther Gomez-Herrero; Montserrat Tobajas; Alicia Polo; Juan J. Rodriguez; Angel F. Mohedano (Environmental Science and Pollution Research, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Intra-organismal variation in the structure of plant vascular transport tissues in poplar trees - Anna L. Jacobsen; Jessica Valdovinos-Ayala; F. Daniela Rodriguez-Zaccaro; M. Angela Hill-Crim; Marta I. Percolla; Martin D. Venturas (Trees, 2018)

Invasive Rhinosinusitis Caused by Lasiodiplodia theobromae in an Allogeneic Hematopoietic Cell Transplant Recipient Case Report and Review of Literature - Anamaria Rodriguez; Shweta Anjan; Octavio V. Martinez; Lazaros J. Lekakis; Amer Beitinjaneh; Jose F. Camargo; Connie F. C. Gibas; Carmita J. Sanders; Nathan P. Wiederhold; Lilian M. Abbo (Mycopathologia, 2018)

Impact of activated sludge acclimation on the biodegradation of toluene absorbed in a hydrophobic ionic liquid - A. S. Rodriguez Castillo; S. Guihéneuf; P.-F. Biard; L. Paquin; A. Amrane; A. Couvert (International Journal of Environmental Science and Technology, 2018)

Adapting clonally propagated crops to climatic changes: a global approach for taro (Colocasia esculenta (L.) Schott) - V. Lebot; V. Tuia; A. Ivancic; G. V. H. Jackson; F. Saborio; G. Reyes; S. Rodriguez; G. Robin; R. Traoré; L. Aboagye; J. Onyeka; W. van Rensburg; et al. (Genetic Resources and Crop Evolution, 2018)

Growth and mortality of larval anchoveta Engraulis ringens , in northern Chile during winter and their relationship with coastal hydrographic conditions - Jorge E. Contreras; Camilo Rodriguez‐Valentino; Mauricio F. Landaeta; Guido Plaza; Manuel I. Castillo; Mónica Alvarado‐Niño (Fisheries Oceanography, 2017)
Larval growth, age, growth effect and instantaneous mortality were estimated in anchoveta, Engraulis ringens , collected biweekly during the austral winter of 2014 in nearshore waters off Bay of Antofagasta (23°41′W–70°30′S), northern Chile. Through measuring standard length ( SL ) and sagitta microstructure analysis, it was estimated that the growth rate of E. ringens larvae decreased from June (0.85 mm day −1 ) to August (0.50 mm day −1 ). However, the water temperature was homogeneous during the sampling dates (14.6, 15.2, 14.4, and 14.6°C), suggesting that the decelerating larval growth was not linked to changes in sea temperature. Additionally, larvae with slow growth have larger otoliths compared with conspecifics with fast growth (growth effect). Larval mortality rates tended to decrease until the middle of July (0.18 per day) but increased to 0.25 per day in early August, which coincided with lower food availability (i.e., chlorophyll‐a, 2.7–5.6 mg m −3 ) and a high occurrence of smaller larvae (1.58–11.5 mm). Partial least squares analysis indicates low covariance between the biological and oceanographic variables ( PLS : 11.71%), suggesting that other factors, such as parental effects, may explain the abrupt decrease in the larval growth rates.

Integrating Science-Based Co-management, Partnerships, Participatory Processes and Stewardship Incentives to Improve the Performance of Small-Scale Fisheries - Kendra A. Karr; Rod Fujita; Ramon Carcamo; Lawrence Epstein; James R. Foley; José A. Fraire-Cervantes; Mauro Gongora; Ollin T. Gonzalez-Cuellar; Pablo Granados-Dieseldorff; Julius Guirjen; Amy H. Weaver; Héctor Licón-González; et al. (Frontiers in Marine Science, 2017)

Photosynthetic performance and pigment composition of Macrocystis pyrifera (Laminariales, Phaeophyceae) along a gradient of depth and seasonality in the ecoregion of Magellan, Chile - J. Marambio; J. P. Rodriguez; F. Mendez; P. Ocaranza; S. Rosenfeld; J. Ojeda; R. Rautenberger; K. Bischof; J. Terrados; A. Mansilla (Journal of Applied Phycology, 2017)

Nutritional properties of dishes prepared with sub-Antarctic macroalgae—an opportunity for healthy eating - Ma. S. Astorga-España; A. Mansilla; J. Ojeda; J. Marambio; S. Rosenfeld; F. Mendez; J. P. Rodriguez; P. Ocaranza (Journal of Applied Phycology, 2017)

Aerobic interval training reduces vascular resistances during submaximal exercise in obese metabolic syndrome individuals - Ricardo Mora-Rodriguez; V. E. Fernandez-Elias; F. Morales-Palomo; J. G. Pallares; M. Ramirez-Jimenez; J. F. Ortega (European Journal of Applied Physiology, 2017)

Imaging Markers of Post-Stroke Depression and Apathy: a Systematic Review and Meta-Analysis - Elles Douven; Sebastian Köhler; Maria M. F. Rodriguez; Julie Staals; Frans R. J. Verhey; Pauline Aalten (Neuropsychology Review, 2017)

Behavioral responses of predaceous minute pirate bugs to tridecane, a volatile emitted by the brown marmorated stink bug - Diego F. Fraga; Joyce Parker; Antonio C. Busoli; George C. Hamilton; Anne L. Nielsen; Cesar Rodriguez-Saona (Journal of Pest Science, 2017)

Ventilator-associated pneumonia by methicillin-susceptible Staphylococcus aureus: do minimum inhibitory concentrations to vancomycin and daptomycin matter? - J. Ruiz-Ramos; P. Vidal-Cortés; A. Díaz-Lamas; R. Reig-Valero; F. Roche-Campo; M. Del Valle-Ortiz; X. Nuvials-Casals; M. Ortiz-Piquer; D. Andaluz-Ojeda; L. Tamayo-Lomas; M. A. Blasco-Navalpotro; M. Rodriguez-Aguirregabiria; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Advantage of multispectral imaging with sub-centimeter resolution in precision agriculture: generalization of training for supervised classification - F. Rodriguez-Moreno; J. Kren; F. Zemek; J. Novak; V. Lukas; M. Pikl (Precision Agriculture, 2017)

Ambulatory blood pressure response to a bout of HIIT in metabolic syndrome patients - M. Ramirez-Jimenez; F. Morales-Palomo; J. G. Pallares; Ricardo Mora-Rodriguez; J. F. Ortega (European Journal of Applied Physiology, 2017)

Salt Marsh and Fringing Oyster Reef Transgression in a Shallow Temperate Estuary: Implications for Restoration, Conservation and Blue Carbon - Justin T. Ridge; Antonio B. Rodriguez; F. Joel Fodrie (Estuaries and Coasts, 2017)

Methylene blue modulates functional connectivity in the human brain - Pavel Rodriguez; Amar P. Singh; Kristen E. Malloy; Wei Zhou; Douglas W. Barrett; Crystal G. Franklin; Wilson B. Altmeyer; Juan E. Gutierrez; Jinqi Li; Betty L. Heyl; Jack L. Lancaster; F. Gonzalez-Lima; et al. (Brain Imaging and Behavior, 2017)

Adaptation of Shigella flexneri to starvation: morphology, outer membrane proteins and lipopolysaccharide changes - K. Chourabi; F. Torrella; S. Kloula; J. A. Rodriguez; I. Trabelsi; S. Campoy; A. Landoulsi; A. Chatti (Arabian Journal of Geosciences, 2017)

Seasonal variations of the photosynthetic activity and pigment concentrations in different reproductive phases of Gigartina skottsbergii (Rhodophyta, Gigartinales) in the Magellan region, sub-Antarctic Chile - J. Marambio; F. Mendez; P. Ocaranza; J. P. Rodriguez; S. Rosenfeld; J. Ojeda; S. Murcia; J. Terrados; K. Bischof; A . Mansilla (Journal of Applied Phycology, 2017)

Epidemiology and reporting of candidaemia in Belgium: a multi-centre study - C. Trouvé; S. Blot; M.-P. Hayette; S. Jonckheere; S. Patteet; H. Rodriguez-Villalobos; F. Symoens; E. Van Wijngaerden; K. Lagrou (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

Consensus Paper: Towards a Systems-Level View of Cerebellar Function: the Interplay Between Cerebellum, Basal Ganglia, and Cortex - Daniele Caligiore; Giovanni Pezzulo; Gianluca Baldassarre; Andreea C. Bostan; Peter L. Strick; Kenji Doya; Rick C. Helmich; Michiel Dirkx; James Houk; Henrik Jörntell; Angel Lago-Rodriguez; Joseph M. Galea; et al. (The Cerebellum, 2017)

Gastrointestinal nematode infection does not affect selection of tropical foliage by goats in a cafeteria trial - J. Ventura-Cordero; P. G. González-Pech; P. R. Jaimez-Rodriguez; G. I. Ortíz-Ocampo; C. A. Sandoval-Castro; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2017)

Sources of trace metals in PM10 from a petrochemical industrial complex in Northern Mexico - P. F. Rodriguez-Espinosa; R. M. Flores-Rangel; V. Mugica-Alvarez; S. S. Morales-Garcia (Air Quality, Atmosphere & Health, 2017)

IFITM3 and severe influenza virus infection. No evidence of genetic association - M. López-Rodríguez; E. Herrera-Ramos; J. Solé-Violán; J. J. Ruíz-Hernández; L. Borderías; J. P. Horcajada; E. Lerma-Chippirraz; O. Rajas; M. Briones; M. C. Pérez-González; M. A. García-Bello; E. López-Granados; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

The influence of slope-angle ratio on the dynamics of granular flows: insights from laboratory experiments - R. Sulpizio; D. Castioni; L. A. Rodriguez-Sedano; D. Sarocchi; F. Lucchi (Bulletin of Volcanology, 2016)

Genotype Number and Allelic Diversity Overview in the National Collection of Chilean Potatoes - M. Muñoz; C. Folch; F. Rodriguez; J. Kalazich; S. Orena; J. Santos; R. Vargas; A. Fahrenkrog; A. Puga (Potato Research, 2016)

Using entropy theory to improve the definition of homogeneous regions in the semi-arid region of Brazil - Renata D.G. Rodriguez; Vijay P. Singh; Fernando F. Pruski; Arthur T. Calegario (Hydrological Sciences Journal, 2016)

Soil mercury levels in the area surrounding the Cerro Prieto geothermal complex, MEXICO - M. A. Pastrana-Corral; F. T. Wakida; E. García-Flores; D. D. Rodriguez-Mendivil; A. Quiñonez-Plaza; T. D. J. Piñon-Colin (Environmental Monitoring and Assessment, 2016)

Oregano Essential Oil as an Antimicrobial and Antioxidant Additive in Food Products - I. Rodriguez-Garcia; B.A. Silva-Espinoza; L.A. Ortega-Ramirez; J.M. Leyva; M.W. Siddiqui; M.R. Cruz-Valenzuela; G.A. Gonzalez-Aguilar; J. F. Ayala-Zavala (Critical Reviews in Food Science and Nutrition, 2016)

Amphibian‐killing chytrid in B razil comprises both locally endemic and globally expanding populations - T. S. Jenkinson; C. M. Betancourt Román; C. Lambertini; A. Valencia‐Aguilar; D. Rodriguez; C. H. L. Nunes‐de‐Almeida; J. Ruggeri; A. M. Belasen; D. da Silva Leite; K. R. Zamudio; J. E. Longcore; L. F. Toledo; et al. (Molecular Ecology, 2016)
Chytridiomycosis, caused by the fungus Batrachochytrium dendrobatidis ( Bd ), is the emerging infectious disease implicated in recent population declines and extinctions of amphibian species worldwide. Bd strains from regions of disease‐associated amphibian decline to date have all belonged to a single, hypervirulent clonal genotype ( Bd ‐ GPL ). However, earlier studies in the Atlantic Forest of southeastern Brazil detected a novel, putatively enzootic lineage ( Bd ‐Brazil), and indicated hybridization between Bd ‐ GPL and Bd ‐Brazil. Here, we characterize the spatial distribution and population history of these sympatric lineages in the Brazilian Atlantic Forest. To investigate the genetic structure of Bd in this region, we collected and genotyped Bd strains along a 2400‐km transect of the Atlantic Forest. Bd ‐Brazil genotypes were restricted to a narrow geographic range in the southern Atlantic Forest, while Bd ‐ GPL strains were widespread and largely geographically unstructured. Bd population genetics in this region support the hypothesis that the recently discovered Brazilian lineage is enzootic in the Atlantic Forest of Brazil and that Bd ‐ GPL is a more recently expanded invasive. We collected additional hybrid isolates that demonstrate the recurrence of hybridization between panzootic and enzootic lineages, thereby confirming the existence of a hybrid zone in the Serra da Graciosa mountain range of Paraná State. Our field observations suggest that Bd ‐ GPL may be more infective towards native Brazilian amphibians, and potentially more effective at dispersing across a fragmented landscape. We also provide further evidence of pathogen translocations mediated by the Brazilian ranaculture industry with implications for regulations and policies on global amphibian trade.

From chemosynthesis-based communities to cold-water corals: Vulnerable deep-sea habitats of the Gulf of Cádiz - José L. Rueda; Emilio González-García; Cinja Krutzky; Francisco J. López-Rodriguez; Gerardo Bruque; Nieves López-González; Desiree Palomino; Ricardo F. Sánchez; Juan Tomás Vázquez; Luis M. Fernández-Salas; Victor Díaz-del-Río (Marine Biodiversity, 2016)

Sulfide-oxidizing bacteria establishment in an innovative microaerobic reactor with an internal silicone membrane for sulfur recovery from wastewater - F. Valdés; P. R. Camiloti; R. P. Rodriguez; T. P. Delforno; J. Carrillo-Reyes; M. Zaiat; D. Jeison (Biodegradation, 2016)

Storm water retention and actual evapotranspiration performances of experimental green roofs in French oceanic climate - D. Yilmaz; M. Sabre; L. Lassabatère; M. Dal; F. Rodriguez (European Journal of Environmental and Civil Engineering, 2016)

IEOOS: the Spanish Institute of Oceanography Observing System - Elena Tel; Rosa Balbin; Jose-Manuel Cabanas; Maria-Jesus Garcia; M. Carmen Garcia-Martinez; Cesar Gonzalez-Pola; Alicia Lavin; Jose-Luis Lopez-Jurado; Carmen Rodriguez; Manuel Ruiz-Villarreal; Ricardo F. Sánchez-Leal; Manuel Vargas-Yáñez; et al. (Ocean Science, 2016)
Since its foundation, 100 years ago, the Spanish Institute of Oceanography (IEO) has been observing and measuring the ocean characteristics. Here is a summary of the initiatives of the IEO in the field of the operational oceanography. Some systems like the tide gauges network has been working for more than 70 years. The standard sections began at different moments depending on the local projects, and nowadays there are more than 180 coastal stations and deep-sea ones that are systematically sampled, obtaining physical and biochemical measurements. At this moment, the Observing System includes six permanent moorings equipped with current meters, an open-sea ocean-meteorological buoy offshore Santander and a sea-surface temperature satellite image station. It also supports the Spanish contribution to the Argo international programme with 47 deployed profilers, and continuous monitoring thermosalinometers, meteorological stations and vessel-mounted acoustic Doppler current profilers on the research vessel fleet. The system is completed with the contribution to the Northwest Iberian peninsula and Gibraltar observatories, and the development of regional prediction models. All these systematic measurements allow the IEO to give responses to ocean research activities, official agencies requirements and industrial and main society demands such as navigation, resource management, risks management, recreation, as well as for management development pollution-related economic activities or marine ecosystems. All these networks are linked to international initiatives, framed largely in supranational programmes of Earth observation sponsored by the United Nations or the European Union. The synchronic observation system permits a spatio-temporal description of some events, such as new deep water formation in the Mediterranean Sea and the injection of heat to intermediate waters in the Bay of Biscay after some colder northern storms in winter 2005.

Estimated Per Capita Water Usage Associated with Different Levels of Water Scarcity Risk in Arid and Semiarid Regions - R. D. G. Rodriguez; F. F. Pruski; V. P. Singh (Water Resources Management, 2016)

Nitric oxide, prostaglandins and angiotensin II in the regulation of renal medullary blood flow during volume expansion - Carol Moreno; María T. Llinás; Francisca Rodriguez; Juan M. Moreno; F. Javier Salazar (Journal of Physiology and Biochemistry, 2016)

Assessing stakeholder impacts and adaptation to low water-levels: the Trent-Severn waterway - J. M. A. Coleman; F. S. Sosa-Rodriguez; L. D. Mortsch; P. J. Deadman (Climatic Change, 2016)

Metal enrichment of soils following the April 2012–2013 eruptive activity of the Popocatépetl volcano, Puebla, Mexico - P. F. Rodriguez-Espinosa; M. P. Jonathan; S. S. Morales-García; Lorena Elizabeth Campos Villegas; E. Martínez-Tavera; N. P. Muñoz-Sevilla; Miguel Alvarado Cardona (Environmental Monitoring and Assessment, 2015)

Microsphere-Based Rapamycin Delivery, Systemic Versus Local Administration in a Rat Model of Renal Ischemia/Reperfusion Injury - Jurjen Zandstra; Marike M. van Beuge; Johan Zuidema; Arjen H. Petersen; Mark Staal; Luisa F. Duque; Sergio Rodriguez; Audrey A. R. Lathuile; Gert J. Veldhuis; Rob Steendam; Ruud A. Bank; Eliane R. Popa (Pharmaceutical Research, 2015)

Relationship between muscle water and glycogen recovery after prolonged exercise in the heat in humans - Valentín E. Fernández-Elías; Juan F. Ortega; Rachael K. Nelson; Ricardo Mora-Rodriguez (European Journal of Applied Physiology, 2015)

Field Evaluation of Transgenic Switchgrass Plants Overexpressing PvMYB4 for Reduced Biomass Recalcitrance - Holly L. Baxter; Charleson R. Poovaiah; Kelsey L. Yee; Mitra Mazarei; Miguel Rodriguez; Olivia A. Thompson; Hui Shen; Geoffrey B. Turner; Stephen R. Decker; Robert W. Sykes; Fang Chen; Mark F. Davis; et al. (BioEnergy Research, 2015)

On the Impact of Intraluminal Thrombus Mechanical Behavior in AAA Passive Mechanics - Fabián Riveros; Giampaolo Martufi; T. Christian Gasser; Jose F. Rodriguez-Matas (Annals of Biomedical Engineering, 2015)

Neighbouring populations, opposite dynamics: influence of body size and environmental variation on the demography of stream-resident brown trout (Salmo trutta) - Albert Fernández-Chacón; Meritxell Genovart; David Álvarez; José M. Cano; Alfredo F. Ojanguren; Rolando Rodriguez-Muñoz; Alfredo G. Nicieza (Oecologia, 2015)

Elimination of Selected Emerging Contaminants by the Combination of Membrane Filtration and Chemical Oxidation Processes - Juan L. Acero; F. Javier Benitez; Francisco J. Real; Elena Rodriguez (Water, Air, & Soil Pollution, 2015)

Analysis of viscoelastic behaviour of rock salt using hydraulic cylinder test - F. Lopez-Gayarre; R. Fernandez-Rodriguez; C. Gonzalez-Nicieza; J. R. Garcia-Menendez (Bulletin of Engineering Geology and the Environment, 2015)

Vertical distribution and migration of fish larvae in the NW Iberian upwelling system during the winter mixing period: implications for cross‐shelf distribution - J.M. Rodriguez; A. Cabrero; J. Gago; C. Guevara‐Fletcher; M. Herrero; A. Hernandez de Rojas; A. Garcia; R. Laiz‐Carrion; A.R. Vergara; P. Alvarez; C. Piñeiro; F. Saborido‐Rey (Fisheries Oceanography, 2015)
The vertical distribution and vertical migrations of fish larvae and implications for their cross‐shelf distribution were investigated in the northern limit of the NE Atlantic upwelling region during the late winter mixing period of 2012. The average positive values of the upwelling index for February and March of this year were far from normal, although the average hydrographic conditions during the period of study were of downwelling and the water column was completely mixed. Fish larvae, most in the preflexion stage, were concentrated in the upper layers of the water column and their distribution was depth stratified, both day and night. However, the larval fish community was not structured in the vertical plane and fish larvae did not show significant diel vertical migration ( DVM ), although five species showed ontogenetic vertical migration. In regions of coastal upwelling and in the absence of DVM , the location of fish larvae in the water column is crucial for their cross‐shelf distribution. Thus, the cross‐shelf distribution of the six most abundant species collected in this study can be explained by the surface onshore flow associated with coastal downwelling, retaining larvae of the coastal spawning species with a relatively shallow distribution in the shelf region and transporting larvae of slope spawning species onto the shelf. The wide vertical distribution shown by larvae of the offshore spawning species could be an adaptation of these species to ensure that some larvae reach the inshore nursery areas.

Is Streptococcus bovis a urinary pathogen? - M. Matesanz; D. Rubal; I. Iñiguez; R. Rabuñal; F. García-Garrote; A. Coira; M. J. García-País; J. Pita; A. Rodriguez-Macias; M. J. López-Álvarez; M. P. Alonso; J. Corredoira (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Detection of hotspots and rapid determination of methane emissions from landfills via a ground-surface method - R. Gonzalez-Valencia; F. Magana-Rodriguez; E. Maldonado; J. Salinas; F. Thalasso (Environmental Monitoring and Assessment, 2015)

Discriminative stimulus and hypothermic effects of some derivatives of the nAChR agonist epibatidine in mice - Jesse S. Rodriguez; Colin S. Cunningham; Fernando B. Moura; Pauline Ondachi; F. Ivy Carroll; Lance R. McMahon (Psychopharmacology, 2014)

Treatment of cosmetic wastewater by a full-scale membrane bioreactor (MBR) - Victor M. Monsalvo; Jesus Lopez; Angel F. Mohedano; Juan J. Rodriguez (Environmental Science and Pollution Research, 2014)

Geomechanical modelling to assess fault integrity at the CO2CRC Otway Project, Australia - C. M. Aruffo; A. Rodriguez-herrera; E. Tenthorey; F. Krzikalla; J. Minton; A. Henk (Australian Journal of Earth Sciences, 2014)

Fear extinction and acute stress reactivity reveal a role of LPA1 receptor in regulating emotional-like behaviors - C. Pedraza; J. Sánchez-López; E. Castilla-Ortega; C. Rosell-Valle; E. Zambrana-Infantes; M. García-Fernández; F. Rodriguez de Fonseca; J. Chun; L. J. Santín; G. Estivill-Torrús (Brain Structure and Function, 2014)

Spatial interpretation of plant parameters in winter wheat - F. Rodriguez-Moreno; V. Lukas; L. Neudert; T. Dryšlová (Precision Agriculture, 2014)

Strategies to evaluate biodegradability: application to chlorinated herbicides - S. Sanchis; A. M. Polo; M. Tobajas; J. J. Rodriguez; A. F. Mohedano (Environmental Science and Pollution Research, 2014)

Comparative study of fuzzy evidential reasoning and fuzzy rule-based approaches: an illustration for water quality assessment in distribution networks - E. Aghaarabi; F. Aminravan; R. Sadiq; M. Hoorfar; M. J. Rodriguez; H. Najjaran (Stochastic Environmental Research and Risk Assessment, 2014)

Long‐term endemism of two highly divergent lineages of the amphibian‐killing fungus in the A tlantic F orest of B razil - D. Rodriguez; C. G. Becker; N. C. Pupin; C. F. B. Haddad; K. R. Zamudio (Molecular Ecology, 2014)
The recent global spread of the amphibian‐killing fungus [ B atrachochytrium dendrobatidis ( Bd )] has been closely tied to anthropogenic activities; however, regional patterns of spread are not completely understood. Using historical samples, we can test whether B d was a spreading or endemic pathogen in a region within a particular time frame, because those two disease states provide different predictions for the regional demographic dynamics and population genetics of B d . Testing historical patterns of pathogen prevalence and population genetics under these predictions is key to understanding the evolution and origin of B d . Focusing on the A tlantic F orest ( AF ) of B razil, we used q PCR assays to determine the presence or absence of B d on 2799 preserved postmetamorphic anurans collected between 1894 and 2010 and used semi‐nested PCR s to determine the frequency of r RNA ITS 1 haplotypes from 52 samples. Our earliest date of detection was 1894. A mean prevalence of 23.9% over time and spatiotemporal patterns of B d clusters indicate that B d has been enzootic in the B razilian AF with no evidence of regional spread within the last 116 years. ITS 1 haplotypes confirm the long‐term presence of two divergent strains of B d ( B d GPL and B d‐Brazil ) and three spatiotemporally broad genetic demes within B d GPL , indicating that B d was not introduced into southeast B razil by the bullfrog trade. Our data show that the evolutionary history and pathogen dynamics of B d in B razil is better explained by the endemic pathogen hypothesis.

Fruit Wastes Fermentation for Phenolic Antioxidants Production and Their Application in Manufacture of Edible Coatings and Films - G. C. G. Martinez-Avila; A. F. Aguilera; S. Saucedo; R. Rojas; R. Rodriguez; C. N. Aguilar (Critical Reviews in Food Science and Nutrition, 2014)

Are HPV vaccination services accessible to high-risk communities? A spatial analysis of HPV-associated cancer and Chlamydia rates and safety-net clinics - Jennifer Tsui; Hector P. Rodriguez; Gilbert C. Gee; Loraine A. Escobedo; Gerald F. Kominski; Roshan Bastani (Cancer Causes & Control, 2013)

A Novel Human Glycoprotein ACA is an Upstream Regulator of Human Hematopoiesis - Z. A. Becker-Kojić; J. R. Ureña-Peralta; R. Saffrich; F. J. Rodriguez-Jiménez; M. P. Rubio; P. Rios; A. Romero; A. D. Ho; M. Stojković (Bulletin of Experimental Biology and Medicine, 2013)

Activation by ACA Induces Pluripotency in Human Blood Progenitor Cells - Z. A. Becker-Kojić; J. R. Ureña-Peralta; I. Zipančić; F. J. Rodriguez-Jiménez; M. P. Rubio; P. Stojković; M. G. Roselló; M. Stojković (Bulletin of Experimental Biology and Medicine, 2013)

CHACO outreach project: the development of a primary health care-based medical genetic service in an Argentinean province - C. Z. Barreiro; M. P. Bidondo; J. A. Garrido; J. Deurloo; E. Acevedo; A. Luna; E. Gutiérrez; C. A. Dellamea; C. Picón; K. Torres; M. F. De Castro; M. V. Torrado; et al. (Journal of Community Genetics, 2013)

ACTH promotes chondrogenic nodule formation and induces transient elevations in intracellular calcium in rat bone marrow cell cultures via MC2-R signaling - Jodi F. Evans; Sylvana Rodriguez; Louis Ragolia (Cell and Tissue Research, 2013)

Human–felid conflict as a further handicap to the conservation of the critically endangered Iberian lynx - Germán Garrote; Guillermo López; José M. Gil-Sánchez; Eva Rojas; Manuel Ruiz; José F. Bueno; Santiago de Lillo; Javier Rodriguez-Siles; José M. Martín; Joaquín Pérez; Maribel García-Tardío; Gerardo Valenzuela; et al. (European Journal of Wildlife Research, 2013)

A Pull-Back Algorithm to Determine the Unloaded Vascular Geometry in Anisotropic Hyperelastic AAA Passive Mechanics - Fabián Riveros; Santanu Chandra; Ender A. Finol; T. Christian Gasser; Jose F. Rodriguez (Annals of Biomedical Engineering, 2013)

Performance evaluation of a new fourth-generation HIV combination antigen–antibody assay - A. Mühlbacher; H. Schennach; J. van Helden; T. Hebell; G. Pantaleo; P. Bürgisser; C. Cellerai; P. Permpikul; M. I. Rodriguez; A. Eiras; F. Alborino; P. Cunningham; et al. (Medical Microbiology and Immunology, 2013)

The droughts of 1997 and 2005 in Amazonia: floodplain hydrology and its potential ecological and human impacts - Javier Tomasella; Patrícia F. Pinho; Laura S. Borma; José A. Marengo; Carlos A. Nobre; Olga R. F. O. Bittencourt; Maria C. R. Prado; Daniel A. Rodriguez; Luz A. Cuartas (Climatic Change, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Comparison of single-dose and extended methamphetamine administration on reversal learning in rats - Alisa R. Kosheleff; Danilo Rodriguez; Steve J. O’Dell; John F. Marshall; Alicia Izquierdo (Psychopharmacology, 2012)

A decision tree for nitrogen application based on a low cost radiometry - F. Rodriguez-Moreno; F. Llera-Cid (Precision Agriculture, 2012)

A comparative assessment of different methods for Landsat 7/ETM+ pansharpening - Victor F. Rodriguez-Galiano; Eulogio Pardo-Igúzquiza; Mario Chica-Olmo; Javier Mateos; Juan P. Rigol-Sánchez; Miguel Vega (International Journal of Remote Sensing, 2012)

Kinetics of biodegradation of diesel fuel by enriched microbial consortia from polluted soils - E. Moliterni; R. G. Jiménez-Tusset; M. Villar Rayo; L. Rodriguez; F. J. Fernández; J. Villaseñor (International Journal of Environmental Science and Technology, 2012)

The Garzón Massif, Colombia-a new ultrahigh-temperature metamorphic complex in the Early Neoproterozoic of northern South America - U. Altenberger; D. M. Mejia Jimenez; C. Günter; G. I. Sierra Rodriguez; F. Scheffler; R. Oberhänsli (Mineralogy and Petrology, 2012)

Feasibility of Different Bioremediation Strategies for Treatment of Clayey and Silty Soils Recently Polluted with Diesel Hydrocarbons - E. Moliterni; L. Rodriguez; F. J. Fernández; J. Villaseñor (Water, Air, & Soil Pollution, 2012)

Aberrant epigenetic regulation of bromodomain Brd4 in human colon cancer - R. M. Rodriguez; C. Huidobro; R. G. Urdinguio; C. Mangas; B. Soldevilla; G. Domínguez; F. Bonilla; A. F. Fernandez; M. F. Fraga (Journal of Molecular Medicine, 2012)

Molecular characterization of Staphylococcus aureus from outpatients in the Caribbean reveals the presence of pandemic clones - A.-C. Uhlemann; C. Dumortier; C. Hafer; B. S. Taylor; J. Sánchez E.; C. Rodriguez-Taveras; P. Leon; R. Rojas; C. Olive; F. D. Lowy (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

An atypical corallum morphology in a species of Pocillopora - A. Rodriguez-Ramirez; F. A. Zapata (Coral Reefs, 2012)

Jatropha adoption: a statistical observational study of factors influencing Malian farmers’ decision to grow Jatropha - M. Basinger; J. Chen; F. Jeffrey-Coker; F. S. Rodriguez-Sanchez; T. Singer; V. Modi (Agroforestry Systems, 2012)

Differences in atmospheric emissions of Poaceae pollen and Lol p 1 allergen - Delia Fernández-González; F. Javier Rodriguez Rajo; Zulima González Parrado; Rosa M. Valencia Barrera; Victoria Jato; Stella Moreno Grau (Aerobiologia, 2011)

Sweat sodium concentration during exercise in the heat in aerobically trained and untrained humans - Nassim Hamouti; Juan Del Coso; Juan F. Ortega; Ricardo Mora-Rodriguez (European Journal of Applied Physiology, 2011)

CIGB-300, a synthetic peptide-based drug that targets the CK2 phosphoaceptor domain. Translational and clinical research - Silvio E. Perea; Idania Baladron; Yanelda Garcia; Yasser Perera; Adlin Lopez; Jorge L. Soriano; Noyde Batista; Aley Palau; Ignacio Hernández; Hernán Farina; Idrian Garcia; Lidia Gonzalez; et al. (Molecular and Cellular Biochemistry, 2011)

Strategies for B-lymphocyte repertoire remodeling in transplantation tolerance - Kumar Vivek; Moiz M. Mustafa; Eduardo Rodriguez; Robert R. Redfield; Ronald F. Parsons; Susan Rostami; Thi-Sau Migone; Michael P. Cancro; Ali Naji; Hooman Noorchashm (Immunologic Research, 2011)

In a hot–dry environment racewalking increases the risk of hyperthermia in comparison to when running at a similar velocity - Ricardo Mora-Rodriguez; Juan F. Ortega; Nassim Hamouti (European Journal of Applied Physiology, 2011)

Expression of HSP70 in Mytilus californianus following exposure to caffeine - Zoe Rodriguez del Rey; Elise F. Granek; Bradley A. Buckley (Ecotoxicology, 2011)

Impact of administration of vancomycin or linezolid to critically ill patients with impaired renal function - O. Rodriguez Colomo; F. Álvarez Lerma; M.I. González Pérez; J-M. Sirvent; M. García Simón (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Communicating with Cancer Patients: What Areas do Physician Assistants Find Most Challenging? - Patricia A. Parker; Alicia C. Ross; Maura N. Polansky; J. Lynn Palmer; M. Alma Rodriguez; Walter F. Baile (Journal of Cancer Education, 2010)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Effects of density, climate, and supplementary forage on body mass and pregnancy rates of female red deer in Spain - P. Rodriguez-Hidalgo; C. Gortazar; F. S. Tortosa; C. Rodriguez-Vigal; Y. Fierro; J. Vicente (Oecologia, 2010)

Aerobically trained individuals have greater increases in rectal temperature than untrained ones during exercise in the heat at similar relative intensities - Ricardo Mora-Rodriguez; Juan Del Coso; Nassim Hamouti; Emma Estevez; Juan F. Ortega (European Journal of Applied Physiology, 2010)

500-year temperature reconstruction in the Mediterranean Basin by means of documentary data and instrumental observations - Dario Camuffo; C. Bertolin; M. Barriendos; F. Dominguez-Castro; C. Cocheo; S. Enzi; M. Sghedoni; A. della Valle; E. Garnier; M.-J. Alcoforado; E. Xoplaki; J. Luterbacher; et al. (Climatic Change, 2010)

Geomorphological reconstruction and morphometric modelling applied to past volcanism - A. Rodriguez-Gonzalez; J. L. Fernandez-Turiel; F. J. Perez-Torrado; D. Gimeno; M. Aulinas (International Journal of Earth Sciences, 2010)

Stimulation of endothelial progenitor cells: a new putative effect of several cardiovascular drugs - Natália António; Rosa Fernandes; Noela Rodriguez-Losada; Manuel F. Jiménez-Navarro; Artur Paiva; Eduardo de Teresa Galván; Lino Gonçalves; Carlos Fontes Ribeiro; Luís A. Providência (European Journal of Clinical Pharmacology, 2010)

Seed treatments enhance photosynthesis in maize seedlings by reducing infection with Fusarium spp. and consequent disease development in maize - C. Rodriguez-Brljevich; C. Kanobe; J. F. Shanahan; A. E. Robertson (European Journal of Plant Pathology, 2010)

A Genomewide Assessment of Inbreeding Depression: Gene Number, Function, and Mode of Action - JULIEN F. AYROLES; KIMBERLY A. HUGHES; KEVIN C. ROWE; MELISSA M. REEDY; SANDRA L. RODRIGUEZ‐ZAS; JENNY M. DRNEVICH; CARLA E. CÁCERES; KEN N. PAIGE (Conservation Biology, 2009)
Although the genetic basis of inbreeding depression is still being debated, most fitness effects are thought to be the result of increased homozygosity for recessive or partially recessive deleterious alleles rather than the loss of overdominant genes. It is unknown how many loci are associated with inbreeding depression, the genes or gene pathways involved, or their mode of action. To uncover genes associated with variation in fitness following inbreeding, we generated a set of inbred lines of Drosophila melanogaster for which only the third chromosome varied among lines and measured male competitive reproductive success among these lines to estimate inbreeding depression. Male competitive reproductive success for different lines validated our prediction that equally inbred lines show variation in inbreeding depression. To begin to assess the molecular basis of inbreeding depression for male competitive reproductive success, we detected variation in whole‐genome gene expression across these inbred lines with commercially available high‐density oligonucleotide microarrays. A total of 567 genes were differentially expressed among these inbred lines, indicating that inbreeding directly or indirectly affects a large number of genes: genes that are disproportionately involved in metabolism, stress and defense responses. Subsequently, we generated a set of outbred lines by crossing the highest inbreeding depression lines to each other and contrasted gene expression between parental inbred lines and F 1 hybrids with transcript abundance as a quantitative phenotype to determine the mode of action of the genes associated with inbreeding depression. Although our results indicated that approximately 75% of all genes involved in inbreeding depression were additive, partially additive, or dominant, about 25% of all genes expressed patterns of overdominance. These results should be viewed with caution given that they may be confounded by issues of statistical inference or associative overdominance.

Shallow lake trophic status linked to late Holocene climate and human impacts - Matthew N. Waters; Michael F. Piehler; Antonio B. Rodriguez; Joseph M. Smoak; Thomas S. Bianchi (Journal of Paleolimnology, 2009)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Proteomic analyses of monocyte-derived macrophages infected with human immunodeficiency virus type 1 primary isolates from Hispanic women with and without cognitive impairment - Dm Toro-Nieves; Y Rodriguez; M Plaud; P Ciborowski; F Duan; J Pérez Laspiur; V Wojna; LM Meléndez (Journal of NeuroVirology, 2009)

CIGB-300, a novel proapoptotic peptide that impairs the CK2 phosphorylation and exhibits anticancer properties both in vitro and in vivo - Silvio E. Perea; Osvaldo Reyes; Idania Baladron; Yasser Perera; Hernán Farina; Jeovanis Gil; Arielis Rodriguez; Dania Bacardi; Jose L. Marcelo; Karelia Cosme; Marisol Cruz; Carmen Valenzuela; et al. (Molecular and Cellular Biochemistry, 2008)

Expression of WUSCHEL in Coffea canephora causes ectopic morphogenesis and increases somatic embryogenesis - A. Arroyo-Herrera; A. Ku Gonzalez; R. Canche Moo; F. R. Quiroz-Figueroa; V. M. Loyola-Vargas; L. C. Rodriguez-Zapata; C. Burgeff D′Hondt; V. M. Suárez-Solís; E. Castaño (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Paleoenvironmental evolution of the Pliocene Villarroya Lake, northern Spain, from stable isotopes and trace-element geochemistry of ostracods and molluscs - P. Anadón; R. Utrilla; A. Vázquez; M. Martín-Rubio; J. Rodriguez-Lázaro; F. Robles (Journal of Paleolimnology, 2008)

Characterization of typo-, regio-, and stereo-selectivities of babaco latex lipase in aqueous and organic media - E. Cambon; J. A. Rodriguez; M. Pina; V. Arondel; F. Carriere; F. Turon; J. Ruales; P. Villeneuve (Biotechnology Letters, 2008)

Economic and management characterization of dehesa farms: implications for their sustainability - P. Gaspar; F. J. Mesías; M. Escribano; A. Rodriguez de Ledesma; F. Pulido (Agroforestry Systems, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Time Course Transformations and Fate of Mercury in Aquatic Model Ecosystems - Emmanuel Tessier; Rosa C. Rodriguez Martin-Doimeadios; David Amouroux; Anne Morin; Christian Lehnhoff; Eric Thybaud; Eric Vindimian; Olivier F. X. Donard (Water, Air, & Soil Pollution, 2007)

Identification of two meridianins from the crude extract of the tunicate Aplidium meridianum by tandem mass spectrometry - A. M. Seldes; M. F. Rodriguez Brasco; L. Hernandez Franco; J. A. Palermo (Natural Product Research, 2007)

Owl monkey MHC-DRB exon 2 reveals high similarity with several HLA-DRB lineages - Carlos F. Suárez; Manuel E. Patarroyo; Esperanza Trujillo; Mónica Estupiñán; Juan E. Baquero; Carlos Parra; Raúl Rodriguez (Immunogenetics, 2006)

Nuclear DNA content of Vitis vinifera cultivars and ploidy level analyses of somatic embryo-derived plants obtained from anther culture - F. Leal; J. Loureiro; E. Rodriguez; M. S. Pais; C. Santos; O. Pinto-Carnide (Plant Cell Reports, 2006)

A Polymerase Chain Reaction Screening Method for Rapid Detection of Microsatellites in Bacterial Artificial Chromosomes - M. F. Rodriguez; S. A. Gahr; C. E. Rexroad; Y. Palti (Marine Biotechnology, 2006)

Owl monkey MHC-DRB exon 2 reveals high similarity with several HLA-DRB lineages - Carlos F. Suárez; Manuel E. Patarroyo; Esperanza Trujillo; Mónica Estupiñán; Juan E. Baquero; Carlos Parra; Raúl Rodriguez (Immunogenetics, 2006)

Can Invasive Species Facilitate Native Species? Evidence of How, When, and Why These Impacts Occur - Laura F. Rodriguez (Biological Invasions, 2006)

Successful treatment of septic shock due to pan-resistant Acinetobacter baumannii using combined antimicrobial therapy including tigecycline - F. S. Taccone; H. Rodriguez-Villalobos; D. De Backer; V. De Moor; J. Deviere; J.-L. Vincent; F. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

The impacts of climate change in coastal marine systems - Christopher D. G. Harley; A. Randall Hughes; Kristin M. Hultgren; Benjamin G. Miner; Cascade J. B. Sorte; Carol S. Thornber; Laura F. Rodriguez; Lars Tomanek; Susan L. Williams (Ecology Letters, 2006)
Anthropogenically induced global climate change has profound implications for marine ecosystems and the economic and social systems that depend upon them. The relationship between temperature and individual performance is reasonably well understood, and much climate‐related research has focused on potential shifts in distribution and abundance driven directly by temperature. However, recent work has revealed that both abiotic changes and biological responses in the ocean will be substantially more complex. For example, changes in ocean chemistry may be more important than changes in temperature for the performance and survival of many organisms. Ocean circulation, which drives larval transport, will also change, with important consequences for population dynamics. Furthermore, climatic impacts on one or a few ‘leverage species’ may result in sweeping community‐level changes. Finally, synergistic effects between climate and other anthropogenic variables, particularly fishing pressure, will likely exacerbate climate‐induced changes. Efforts to manage and conserve living marine systems in the face of climate change will require improvements to the existing predictive framework. Key directions for future research include identifying key demographic transitions that influence population dynamics, predicting changes in the community‐level impacts of ecologically dominant species, incorporating populations’ ability to evolve (adapt), and understanding the scales over which climate will change and living systems will respond.

Genome-wide SNP discovery and linkage analysis in barley based on genes responsive to abiotic stress - Nils Rostoks; Sharon Mudie; Linda Cardle; Joanne Russell; Luke Ramsay; Allan Booth; Jan T. Svensson; Steve I. Wanamaker; Harkamal Walia; Edmundo M. Rodriguez; Peter E. Hedley; Hui Liu; et al. (Molecular Genetics and Genomics, 2005)

Characterization of Toll-like receptor 3 gene in rainbow trout (Oncorhynchus mykiss) - M. F. Rodriguez; G. D. Wiens; M. K. Purcell; Y. Palti (Immunogenetics, 2005)

Clinical characteristics and significance of Streptococcus salivarius bacteremia and Streptococcus bovis bacteremia: a prospective 16-year study - J. C. Corredoira; M. P. Alonso; J. F. García; E. Casariego; A. Coira; A. Rodriguez; J. Pita; C. Louzao; B. Pombo; M. J. López; J. Varela (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Vocal dialects, sex‐biased dispersal, and microsatellite population structure in the parrot Amazona auropalliata - TIMOTHY F. WRIGHT; ANGELICA M. RODRIGUEZ; ROBERT C. FLEISCHER (Molecular Ecology, 2005)
Geographic variation in microsatellite allele frequencies was assessed at nine sites in two regional vocal dialects of the parrot Amazona auropalliata (yellow‐naped amazon) to test for correspondence between dialects and population structure. There was no relationship between the genetic distances between individuals and their dialect membership. High rates of gene flow were estimated between vocal dialects based on genetic differentiation. In addition, 5.5% of pairs of individuals compared across the dialect boundary were estimated to be related at the level of half siblings, indicating that dispersal is ongoing. The number of effective migrants per generation between dialects estimated with the microsatellite data was roughly one‐seventh the number estimated with mitochondrial control region sequence data from the same individuals, suggesting that gene flow may be female‐biased. Together, these results suggest that the observed mosaic pattern of geographic variation in vocalizations is maintained by learning of local call types by immigrant birds after dispersal. We found no evidence that ongoing habitat fragmentation has contributed to cryptic population structure.

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

Environmental Education as a Component of Multidisciplinary Conservation Programs: Lessons from Conservation Initiatives for Critically Endangered Fruit Bats in the Western Indian Ocean - W. J. TREWHELLA; K. M. RODRIGUEZ‐CLARK; N. CORP; A. ENTWISTLE; S. R. T. GARRETT; E. GRANEK; K. L. LENGEL; M. J. RABOUDE; P. F. REASON; B. J. SEWALL (Conservation Biology, 2005)
Pteropus livingstonii , P. voeltzkowi , and P. rodricensis are three critically endangered fruit bats from western Indian Ocean islands for which multidisciplinary conservation programs have been established that include environmental education programs (EEPs). We describe these EEPs in terms of the strategies used to achieve them and evaluate the educational and conservation outcomes and impacts of the programs. Educational outputs (including posters, stickers, videos, lesson plans, and workshops), primarily linking human needs to the ecosystem services provided by bats, were delivered to schools and community groups, and local environmental educators were trained to further develop the EEPs. Outcomes included increased local awareness about the bats and their conservation, training of environmental educators, inclusion of bat conservation and environmental issues in the school curricula, and establishment of community‐based environmental nongovernmental organizations (NGOs). Extensive prior planning, presentations in local languages, distribution of outputs through existing networks of educators, training of local educators, establishment of local environmental NGOs, and local capacity‐building were all associated with these EEPs achieving their goals in the under‐resourced island locations where these bats are found. The EEPs were also important in the development of other components of their respective conservation programs, such as population monitoring programs. Although long‐term conservation impacts, particularly tackling habitat loss, are slow to materialize and social and economic issues need to be addressed, these EEPs have already had important outcomes and have established the foundation for future conservation actions.

High-resolution Numerical Simulation of Flow Through a Highly Sinuous River Reach - José F. Rodriguez; Fabián A. Bombardelli; Marcelo H. García; Kelly M. Frothingham; Bruce L. Rhoads; Jorge D. Abad (Water Resources Management, 2004)

Effects of lindane on the photosynthetic apparatus of the cyanobacteriumanabaena - Marta Bueno; Maria F. Fillat; Reto J. Strasser; Ronald Maldonado-Rodriguez; Nerea Marina; Henry Smienk; Carlos Gómez-Moreno; Francisco Barja (Environmental Science and Pollution Research, 2004)

Haemophilus parainfluenzae : an Underdiagnosed Pathogen of Biliary Tract Infections? - J. Frankard; H. Rodriguez-Villalobos; M. J. Struelens; F. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Spatial and Seasonal Variations of Water Quality in a Mediterranean Catchment: The Llobregat River (NE Spain) - J.L. Fernández-Turiel; D. Gimeno; J.J. Rodriguez; M. Carnicero; F. Valero (Environmental Geochemistry and Health, 2003)

Characterization of the RNA-binding activity of VP3, a major structural protein of Infectious bursal disease virus - G. Kochan; D. Gonzalez; J. F. Rodriguez (Archives of Virology, 2003)

Effects of Sertoli cell transplants in a 3-nitropropionic acid model of early Huntington's disease: a preliminary study - Alba I. Rodriguez; Alison E. Willing; Samuel Saporta; Don F. Cameron; Paul R. Sanberg (Neurotoxicity Research, 2003)

Mineralization of Clapper Rail Eggshell from a Contaminated Salt Marsh System - A. B. Rodriguez-Navarro; K. F. Gaines; C. S. Romanek; G. R. Masson (Archives of Environmental Contamination and Toxicology, 2002)

The Bayesian approach applied to GPS ambiguity resolution. A mixture model for the discrete-real ambiguities alternative - M. C. de Lacy; F. Sansò; G. Rodriguez-Caderot; A. J. Gil (Journal of Geodesy, 2002)

Cross Reaction Between a Pan-Candida Genus Probe and Fusarium Spp. in a Fatal Case of Fusarium oxysporum Pneumonia - H. Rodriguez-Villalobos; M. Aoun; C. Heymans; J. De Bruyne; V. Duchateau; J. Verdebout; F. Crokaert (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Molecular linkage mapping in rye (Secale cereale L.) - X.-F. Ma; M. K. Wanous; K. Houchins; M. A. Rodriguez Milla; P. G. Goicoechea; Z. Wang; M. Xie; J. P. Gustafson (Theoretical and Applied Genetics, 2001)

Mitochondrial DNA control region diversity in the endangered blue chaffinch, Fringilla teydea - J. Pestano; R. P. Brown; F. Rodriguez; A. Moreno (Molecular Ecology, 2000)
The blue chaffinch ( Fringilla teydea ) is found only on the two central Canary Islands of Gran Canaria and Tenerife, where it is restricted to pine forest habitat. It is reasonably abundant on the latter island but endangered on the former. Here, sequence variation was studied in a fragment spanning domains I and II of the mitochondrial DNA (mtDNA) control region. Phylogenetic analysis of all haplotypes with a F. coelebs outgroup indicated the two island populations were reciprocally monophyletic, supporting their individual conservation. Unlike in other species, most within‐island haplotype diversity was due to mutations in the domain II region. Surprisingly, genetic diversity was greater in the smaller Gran Canarian population. We suggest that this is unlikely to be maintained under current population sizes although it may be mitigated by incorporating genetic information into the captive breeding programme.

Relative and combined effects of ethanol and protein deficiency on strontium and barium bone content and fecal and urinary excretion - E. Gonzalez-Reimers; F. Rodriguez-Moreno; A. Martinez-Riera; A. Mas-Pascual; E. Delgado-Ureta; L. Galindo-Martin; M. Arnay-de La Rosa; F. Santolaria-Fernandez (Biological Trace Element Research, 1999)

Monthly mean pressure reconstructions for Europe for the 1780–1995 period - P.D. Jones; T.D. Davies; D.H. Lister; V. Slonosky; T. Jónsson; L. Bärring; P. Jönsson; P. Maheras; F. Kolyva‐Machera; M. Barriendos; J. Martin‐Vide; R. Rodriguez; et al. (International Journal of Climatology, 1999)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Candida and Bacterial Mandibular Osteomyelitis in an AIDS-Patient - C. Sanz-Rodriguez; F. Hernandez-Surmann; A. G. Bueno; C. Goizueta; A. Noguerado (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Letters - Timothy D. Male; Reed F. Noss; Timothy M. Crowe; Jon Paul Rodriguez; Gary K. Meffe (Conservation Biology, 1998)

Candida and bacterial mandibular osteomyelitis in an AIDS patient - C. Sanz-Rodriguez; F. Hernandez-Surmann; A. G. Bueno; C. Goizueta; A. Noguerado (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Neurological and functional effects of short-term exposure to hand-arm vibration - J. Malchaire; L. S. Rodriguez Diaz; A. Piette; F. Gonçalves Amaral; D. de Schaetzen (International Archives of Occupational and Environmental Health, 1998)

Novel Antifeedant and Insecticidal Compounds from Avocado Idioblast Cell Oil - Cesar Rodriguez-Saona; Jocelyn G. Millar; David F. Maynard; John T. Trumble (Journal of Chemical Ecology, 1998)

The structure of carbonyl horseradish peroxidase: spectroscopic and kinetic characterization of the carbon monoxide complexes of His-42 → Leu and Arg-38 → Leu mutants - Jose Neptuno Rodriguez-Lopez; Simon J. George; R. N. F. Thorneley (JBIC Journal of Biological Inorganic Chemistry, 1998)

Metallothionein-like metalloproteins in the Baltic clam Macoma balthica : seasonal variations and induction upon metal exposure - G. Bordin; J. McCourt; F. Cordeiro Raposo; A. R. Rodriguez (Marine Biology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

A molecular genetic map of cassava (Manihot esculenta Crantz) - M. Fregene; F. Angel; R. Gomez; F. Rodriguez; P. Chavarriaga; W. Roca; J. Tohme; M. Bonierbale (Theoretical and Applied Genetics, 1997)

Changes in carbon isotope discrimination in grain cereals from different regions of the western Mediterranean Basin during the past seven millennia. Palaeoenvironmental evidence of a differential change in aridity during the late Holocene - J.L. ARAUS; A. FEBRERO; R. BUXO; M.D. CAMALICH; D. MARTIN; F. MOLINA; M.O. RODRIGUEZ‐ARIZA; I. ROMAGOSA (Global Change Biology, 1997)
Carbon isotope discrimination (Δ) was determined for kernels of six‐row barley and durum wheat cultivated in the western Mediterranean basin during the last seven millennia. Samples came from different archaeological sites in Catalonia (north‐east Spain) and in the south‐east of Spain (mainly eastern Andalusia). Samples from the present were also analysed. Mean values of Δ for barley and durum wheat grains decreased slightly from Neolithic (7000–5000 BP) to Chalcolithic‐Bronze (5000–3000 BP) and Iron ages (3000–2200 BP) both in Catalonia and in south‐east (SE) Spain. Values were consistently lower in SE Spain than in Catalonia throughout these five millennia, which suggests that Catalonia was less arid than SE Spain in this period. Within a given region, current discrimination values for kernels of the same cereal species cultivated under rainfed conditions were lower than those of archaeological grains, which implies more arid conditions at present. Furthermore, an empirical relationship between Δ of mature kernels and total precipitation (plus irrigation where applicable) during grain filling ( r 2 = 0.73, N = 25) was established for barley, currently cultivated at different locations in the western Mediterranean basin in Spain. The resulting relationship was applied to the Δ data for barley kernels from 10 archaeological sites in Catalonia and 10 sites in SE Spain, to estimate the precipitation during grain filling at the time the kernels were produced. For both regions, current climatic conditions are consistently more arid than those inferred for the Neolithic, Bronze and Iron ages. In addition, although Catalonia was estimated to have had consistently wetter conditions (about 20% more precipitation) than SE Spain throughout these millennia, differences in precipitation between these two regions have recently increased, with 79% more precipitation in Catalonia. Results indicate a more rapid increase in aridity in SE Spain than in Catalonia, probably produced during the last few centuries, and due to anthropogenic causes.

Analysis of sites of foot and mouth disease virus persistence in carrier cattle via the polymerase chain reaction - M. L. Prato Murphy; R. F. Meyer; C. Mebus; A. A. Schudel; M. Rodriguez (Archives of Virology, 1994)

Book reviews - Jon F. Hunter; J. G. Llaurado; Jean O'Connor Dorsi; William M. Chilian; Harcharan Singh Ranu; David J. Pogue; Carlos A. Rodriguez-Garcia (Annals of Biomedical Engineering, 1990)

Studies on the mechanism of entry of vaccinia virus in animal cells - R. A. Janeczko; J. F. Rodriguez; M. Esteban (Archives of Virology, 1987)

Human cytomegalovirus persists in cells treated with interferon - J. E. Rodriguez; T. R. Loepfe; M. F. Stinski (Archives of Virology, 1983)

Imide derivatives of 3-nitro-1.8-naphthalic acid: Their inhibitory activity against DNA viruses - A. Garca Gancedo; C. Gil-Fernndez; P. Vilas; S. Perez; E. Paez; F. Rodriguez; M. F. Braa; C. M. Roldn (Archives of Virology, 1982)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)